Mechanisms of taVNS-induced working memory enhancement: a multimodal fNIRS–HRV–MEP study - Menghuan Wang; Wewei Dou; Xiang Gong; Yunjie Gui; Feng Lin; Dandan Liang (Cognitive Neurodynamics, 2026)

Melatonin attenuates gentamicin-induced cochlear hair cell injury by modulating the cGAS–STING signaling pathway - Han-gui Lu; Shuang-le Wang; Guo-feng Wen; Chuang-wei Li; Xin-sheng Lin (Tissue and Cell, 2026)

Sex peptide receptor modulates sex pheromone perception plasticity in female Galleria mellonella across mating status - Zhen-Ping Guo; Xu-Dong Pang; Li-Lin Luo; Ming-Qing Yu; Jun-Hong Linghu; Hua-Yan Xie; Guy Smagghe; Tong-Xian Liu; Shun-Hua Gui (Insect Biochemistry and Molecular Biology, 2026)

Delta dynamics: Insights from high-density OSL chronology in the Han River Delta, Northern South China Sea - Ping Lai; Gui Long; Tiantian Huang; Guanjun Xu; Zibin Fang; Ziyuan Wu; Yuexin Liu; Penghui Lin; Xiwen Nong; Xiaojian Zeng; Hongwei Li; Zhongping Lai (Geomorphology, 2026)

Contrasting impacts of biodegradable and conventional microplastics on heavy metal bioavailability in soils: A multilevel meta-analysis - Xue-Dan Cui; Zheng-Xiao Jiang; Yi-Hao Mei; Ting-Ting He; Xiao Tan; Ai-Jun Lin; Gui-Lan Duan (Environmental Pollution, 2026)

An auxetic trampoline metamaterial with tunable bandgap under prestrain - Tong Cheng; Gui Lei Chen; Wei Zhong Jiang; Yi Zhang; Xiang Jie Wei; Zhu Kun Mi; Xiao Ji; Lin Hua; Jia Hui Zhang; Shu Hao Song; Cheng Shen; Xin Ren (Engineering Structures, 2026)

A novel efficient numerical method for 3D bi-anisotropic photonic crystal simulation - Ke Gui; Tiexiang Li; Wen-Wei Lin; Xing-Long Lyu (Computer Physics Communications, 2026)

Interfacial charge redistribution at ZnSe/V2O5 heterojunction encapsulated in N, P-doped carbon enables high-performance wide-temperature Zn-air batteries - Mingjie Yi; Shuanghui Lv; Leqian Chu; Jingwen Zhang; Lijun Lin; Liangqi Gui; Jing Huang; Jiaheng Zhang (Chemical Engineering Journal, 2026)

Development of TM hypoallergenic enzymatic products with the potential to induce immune tolerance in Lateolabrax japonicus - Meng-Si Li; Qing-Mei Liu; Fei Xia; Su-Jie Huang; Shun-Xian Lin; Li-Qiang Zhong; Hao-Tian Zhang; Gui-Xia Chen; Guang-Ming Liu (Food Bioscience, 2026)

Photothermal-promoted formic acid dehydrogenation over PdCu nanoalloys enabled by alloy-induced electronic modulation - Ziyan Sun; Linghao Yu; Yuan Lin; Yunyun Gui; Yashi Chen; Lijun Liu (Chemical Engineering Journal, 2026)

Oral self-assembled nanomedicine orchestrates hierarchical regulation of the lipid–ROS–inflammation cascade for comprehensive therapy of non-alcoholic fatty liver disease - Jia-Jian Zhang; Yin-Sheng Tan; Chen-Lei Zhang; Yan Gui; Fan-Zhi Yan; Jie Hou; Xiang-Xuan Liu; Hua Kong; Meng-Ru Guo; Yang-Feng Cui; Xian-He Lin; Tao-Tao Fan; et al. (Chemical Engineering Journal, 2026)

Outdoor light at night exposure and hypertension risk in adults: A longitudinal cohort study from the FLORA project - Shuo Zhang; Xiao-Fan Lu; Muhammad Amjad; Lin-Jing Gong; Na Liu; Hong-Xing Zou; Xiao-Yi Liu; Le-Bing Wang; Yuan-Yuan Fan; Yang-Yang Li; Yi-Ran Chen; Wen-Wen Bao; et al. (Environmental Research, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Effects of norgestrel on the reproductive endocrine system, hepatic damage and antioxidant responses of marine medaka (Oryzias melastigma) at different salinities - Jian Song; Chao Zheng; Yan-Qiu Liang; Zhongdian Dong; Chang-Gui Pan; Wen-Jun Shi; Qidan Zheng; Shuhui Zhou; Mingwei He; Xipeng Mo; Zhong Lin (Aquatic Toxicology, 2026)

Proteomic comparison of human neural cell-derived extracellular vesicles and parental cells from Alzheimer’s disease and cognitively normal individuals - Jia-Yan Xin; Jie Liu; Hao-Min Dong; Hai-Lun Yu; Zhong-Song Xiao; Jian-Ni Hu; Qiu Jiang; Yu-Peng Zhu; Lin Feng; Yun Feng; Yu-Juan Jia; Zi-Yu Yuan; et al. (Science China Life Sciences, 2026)

Trophic plasticity drives species-specific adaptive responses to seasonal variability in reef-building corals - Xiao-Lei Yu; Lei Jiang; Yong Luo; Lin-Tao Huang; Peng Zhang; Zhan-Wei Li; Cheng-Yue Liu; Pan Zhang; Jian-Yu Chen; Sheng Liu; Gui-Xin Dong; Hui Huang (Coral Reefs, 2026)

Undescribed triterpenoid ellagitannins from Castanopsis calathiformis and their potential antiproliferative and hypoglycemic activity - Ya-feng Wang; Ying-rong Bao; Rui-jie He; Nao Pang; Zhang-bin Liu; Bing-yuan Yang; Gui-qin Li; Yong-lin Huang (Phytochemistry, 2026)

Characterization of fluxapyroxad-induced cardiotoxicity in zebrafish - Huilin Yu; Aijun Gui; Zhenkun Zhang; Juan Xu; Xueqian Wu; Menghui Lin; Haiying Cai; Junhui Zhang (Journal of Environmental Sciences, 2026)

A constitutive model incorporating particle breakage and strain rate effects for carbonate sand subjected to dynamic loading - Jianjun Ma; Yize Kang; Yilin Gui; Weizhen Huang; Linchong Huang; Yuexiang Lin (Computers and Geotechnics, 2026)

Egg and early-instar morphology of Lymantria juglandis (Lepidoptera: Erebidae: Lymantriinae): Insights into its functional implications - Ya-Xin Cao; Jing-Bang Liu; Pan-Pan Zhang; Gui-Lin Hu (Arthropod Structure & Development, 2026)

A comprehensive review on the chemical composition, pharmacological effects and quality evaluation of Gentiana straminea Maxim. - Yuan-Wen Zhuang; Min Wang; Jian-Tao Zhao; Yu-Qing Wang; Run-Qian Yu; Huan Xia; Xiao-Hong Wei; Peng-Cheng Lin; Gui-Yang Xia; Sheng Lin (Journal of Natural Medicines, 2026)

Effect of Excavation Sequence and Bolt Support on Surrounding-Rock Stability of a Double-Tunnel System in Jointed Rock Mass - Feng Jiang; Tian-lin Huang; Hai-zhen Huang; Ji-song Wang; Peng He; Gang Wang; Chun-gui Li; Ting-fang Liu; Cheng-cheng Zheng; Zhi-yong Xiao (Applied Geophysics, 2026)

Non-equilibrium criticality-enhanced quantum sensing with superconducting qubits - Hao Li; Yaoling Yang; Yun-Hao Shi; Zheng-An Wang; Ziting Wang; Jintao Li; Yipeng Zhang; Kui Zhao; Yueshan Xu; Cheng-Lin Deng; Yu Liu; Wei-Guo Ma; et al. (Science Bulletin, 2026)

Boosting char formation in lignin aerogels via PN synergy: A route to flame retardancy and multifunctional performance - Jia-Hui Wang; Tao Gui; Shuang-Lin Zou; Qing-Hua Wang; Ying-Chun Xu; Rong Tan; Qiang Wang; Ling-Ping Xiao; Run-Cang Sun (Chemical Engineering Journal, 2026)

Comparative Proteomic Insights into Low Molecular Weight Chitosan-Induced Drought Tolerance in Sugarcane - Gui Zhou; Xiao-Xia Liu; Li-Hang Qiu; Cheng-Lin Zou; Yang-Rui Li (Sugar Tech, 2026)

Structurally diverse monoterpenoid indole alkaloids from Damnacanthus hainanensis as well as their potential anti-inflammatory and anti-HIV effects - Gui-Qiong Wu; Long-Cheng Cui; Ye-Ping Liu; Chen-Xu Yue; Lin-Xuan Li; Tian-Yu Wang; Yu-Shan Wang; Shu-Ri Li; Yan-Ping Liu; Yan-Hui Fu (Natural Product Research, 2026)

Characteristics of structural superimposed halo at the Jiawula Ag-Pb-Zn deposit, Inner Mongolia, China and its significance for exploration - Xin-yu Gao; Gui-yuan Sun; Kang Wang; Wei Zhang; Zhi-ping Li; Wen-ju Li; Jiang Wei; Lin Yang; Hong-zhe Xie; Zi-wen Yang; Chao Ma (Journal of Geochemical Exploration, 2026)

Genetic deletion of miR-200a/200b increases growth and feed conversion efficiency in yellow catfish - Xu Wang; Yan Xie; Qiaohong Lin; Yang Xiong; Ying Liu; Si Ge; Qiuen Tan; Zhipeng He; Youbo Jiang; Qingqing Han; Shuang Jin; Peipei Huang; et al. (Science China Life Sciences, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Achieving “one stone, three birds”: A solid-waste steel-slag-derived system for synergistic antibiotic degradation and CO2 capture - Shiping Zhang; Xiaoyong Wu; Baolin Zhao; Gui Yang; Shenxu Bao; Xueying Chen; Ling Xia; Yao Wang; Juan Long; Yang Wu; Lin Wang; Binbin He (Journal of Cleaner Production, 2026)

TiO2 phase-regulated Pd–H chemistry: Balancing active hydrogen production and utilization - Shuai Zhu; Xujia Cao; Zhengxu Yan; Yuan Lin; Yunyun Gui; Lijun Liu (Journal of Environmental Chemical Engineering, 2026)

Boosting catalytic transfer hydrogenation via d-band engineering in Ag/CeO2 nanobelts using formaldehyde as hydrogen donor - Rongjie Cai; Ziyan Sun; Yuan Lin; Yunyun Gui; Lijun Liu (Journal of Environmental Chemical Engineering, 2026)

Expression, characterization and antibacterial effects of two endolysins as novel biocontrol agents against Pseudomonas oleovorans in foods - Junxin Zhao; Tonglei Zhou; Yiming Xu; Mengfei Duan; Zheng Zhao; Jingyi Gui; Didi Guo; Xinshuo Yang; Deguo Wang; Yunzhi Lin; Su Zar Chi Lwin; Yoshimitsu Masuda; et al. (International Journal of Food Microbiology, 2026)

The relative roles of cell size and phylogeny in driving dissimilarity of algal functional trait - Qiang He; Bin Chen; Kai-Kai Deng; Peng Yan; Gui-Jiao Lin; Qiu-Wen Chen; You-Peng Chen; Jin-Song Guo (Bioresource Technology, 2026)

Infra-slow body-surface potentials show a group-level association with thyroid cancer - Bohan Deng; Ruili Zhang; Yuxuan Liu; Jinglao Lin; Shicong Gui; Xihao Wei; Yin Cheng; Li Zheng; Shaohua Hu; Pingping Lyu; Yubo Li; Huafen Wang (Journal of Zhejiang University-SCIENCE B, 2026)

Benzyl isothiocyanate inhibits the conjugative transfer of mcr-1-positive plasmid via suppressing intercellular contact and limiting energy supply - Ping Cheng; Shuying Liang; Shixin Gui; Xinyu Wang; Lingfeng Yu; Wenjun Cui; Chunxu Lu; Lin Li (Journal of Environmental Management, 2026)

Identifying the genesis and evolution of geothermal water in the coal mining area, North China: Insights from hydrochemistry and δ2H, δ18O, δ13C, δ34S and 87Sr/86Sr isotopes - Jie Zhang; Herong Gui; Luwang Chen; Manli Lin; Huifang Rong; Jun Li; Ruirui Li; Mingda Cao (Geothermics, 2026)

Relationship of serum polycyclic aromatic hydrocarbon (PAHs) and lung function in adults: Evidence from a large community-based population in Guangzhou, China - Jing-Lin Zhang; Nuo Chen; Shui-Yue Lu; Michael S. Bloom; Shao Lin; Lu-Yin Wu; Li-Xia Liang; Yun-Ting Zhang; Jing-Wen Huang; Muhammad Amjad; Yong-Xiang Tang; Zhao-Huan Gui; et al. (Environmental Research, 2026)

MdERF106 modulates malate accumulation in apple fruit by activating MdALMT9 - Xu Xu; Lin Zhao; Renzhi Gui; Weihong Fu; Sanhong Wang (Plant Cell, Tissue and Organ Culture (PCTOC), 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Constructing Ce–O–C covalent-bridged S-scheme heterojunction via molten-salt transformation of Ce-MOF for photocatalytic overall H2O2 synthesis - Ziying Feng; Pengjia Li; Dou Yang; Jingyi Yu; Yunyun Gui; Shao-Chuan Li; Yuan Lin; Junhua Zou; Lijun Liu (Journal of Environmental Chemical Engineering, 2026)

Impact of algal blooms on phosphorus migration: Insights from laboratory and field cultivation enrichment experiments in the yangtze river estuary - Yu-Yuan Wang; Zhi-Li Guo; Han-Lin Jiang; Yuan-Zhe Ni; Li-Min Zhou; Gui-Peng Yang; Xiao-Yan Cao (Estuarine, Coastal and Shelf Science, 2026)

Evolution of tactoid structures and pore water distribution during wetting in saturated clay aggregates driven by montmorillonite-water interaction - Kai-wen Tong; Chang-fu Wei; Yong-gui Chen; Zi-yu Ding; Hao Wang; Ya-kun Tian; Rong Gui; Ling-ling Wu; Zhi-jun Zhang; Lin Hu (Computers and Geotechnics, 2026)

Defect passivation with Pb for high-performance Sb2S3 solar cells via vapor transport deposition - Gan Huang; Xin-Yi Cai; Hu Li; Jin-Rui Cai; Ying-Sen Xia; Zhi-Ping Huang; Li-Mei Lin; Fu-Bao Gong; Shui-Yuan Chen; Gui-Lin Chen (Chemical Engineering Journal, 2026)

Low C/N organic residues enhance reductive soil disinfestation for the suppression of Ralstonia solanacearum - Hui-Juan Duan; Yue Yin; Jun Zhao; Xian-Yong Lin; Gui-Lan Duan (Plant and Soil, 2026)

Psychromicrobium ferritrahens sp. nov., A Novel Actinobacterium Isolated from Decayed Wood in Shizong County, China - Lin-Bo Zhang; Jiang-Yuan Zhao; Yong-Jie Zeng; Hong-Bo Zha; Lin Gong; Pei-Wen Yang; Zhang-Gui Ding; Ming-Gang Li; Shun-Bo Gao; Le-Le Li; Shu-Kun Tang (Current Microbiology, 2026)

Stage-specific neurotoxicity of lead in zebrafish: Metabolic disruption in embryos and ferroptosis in larvae - Jian Liu; Guizhen Yan; Hengyu Gui; Kang Luo; Hongwei Liang; Ai Guan; Weizhen Liu; Hongyu Zhou; Zhang Lin; Bing Yan (Journal of Hazardous Materials, 2026)

Long-term ozone exposure and attention-deficit/hyperactivity disorder symptoms in school-aged children: Findings from a large multi-city study in China - Zhao-Huan Gui; Wan-Ting He; Yun-Ting Zhang; Joachim Heinrich; Michael S. Bloom; Shao Lin; Bin Jalaludin; Mohammed Zeeshan; Lidia Morawska; Tian-Yu Zhao; Shyamali Dharmage; Luke Knibbs; et al. (Journal of Hazardous Materials, 2026)

Machine learning-assisted sensor array based on enhanced dual enzyme-like activities of Fe SAzymes modulated via Pluronic surfactant for multi-category perfluoroalkyl intelligent recognition and quantification - Wen-Cai Jiang; Xiao-Mei Li; Jia-Hao Cheng; Li-Yao Xu; Ri-Za He; Gui-Lin Zou; Zhi-Bo Hou; Yan Zhao; Guo-Qi Zhang (Chemical Engineering Journal, 2026)

AI-driven framework for high-precision seamless sunshine duration estimation using Himawari-8 satellite and ground observations - Honglei Wu; Zhaohua Liu; Zhaoliang Zeng; Ke Gui; Zhijian Lin; Peng Xie; Ruqing Zhu; Zhehao Liang; Yaqiang Wang; Huizheng Che (Atmospheric Research, 2026)

Field and laboratory investigations of the fluid in fully developed debris flows - Xiao Su; Ze-Min Xu; Yi-Xi Wen; Bin Li; Jing-Kai Meng; Lin Tian; Zi-Ming Ye; Gui-E Shi (Bulletin of Engineering Geology and the Environment, 2026)

Controls and contributions of methylotrophic methanogenesis to methane production in coastal sediments - Guang‐Chao Zhuang; Qiao Liu; Lin Yuan; Bingzheng Wu; Xiuqi Sui; Zhen Zhou; Jinyan Wang; Liang Dong; Xiting Liu; Gui‐Peng Yang; Fengping Wang (Limnology and Oceanography, 2026)
Methylotrophic methanogenesis has recently been recognized as a key process driving cryptic methane cycling within sulfate‐reducing sediments. Here we conducted biogeochemical analyses of methanogenic substrates, activity, and communities in two sediment cores (4–5 m) from the East China Sea, to constrain the dynamics and controls of methylotrophic methanogenesis in coastal sediments. We detected micromolar concentrations of methane in the presence of sulfate and high methane concentrations (up to 4.2 mM) below the sulfate–methane transition zone (~ 150–170 cm). Stable isotope composition of methane was strongly depleted (−77‰ to −91‰), indicating its biological production. Methanogenic substrates including H 2 /CO 2 , acetate, and methylated compounds were detected in the porewaters and/or sediments. Radiotracer experiments indicated methane production from various substrates, and the presence of sulfate did not inhibit methanogenesis at either site. At the coastal site with the dominance of marine organic matter (total organic carbon: 0.6%; C/N ratio: ~ 6.4; δ 13 C‐total organic carbon: −22‰), methane was primarily produced from hydrogenotrophic methanogenesis, consistent with the progressive enrichment of 13 C in dissolved inorganic carbon with depth below the sulfate–methane transition zone. However, methylotrophic methanogenesis from methanol and trimethylamine contributed significantly to methane production (up to 30.2%) at the estuarine site (total organic carbon: 0.5%; C/N ratio: 7.4, δ 13 C‐total organic carbon: −23‰) with elevated terrestrial organic matter input, also reflected from the predominance of long chain odd carbon n‐alkanes. These findings suggested that organic carbon source and composition, instead of sulfate, control methanogenic activity, providing evidence that high terrestrial organic inputs could significantly enhance methylotrophic methanogenesis in coastal sediments.

Exploring the complexities of bitterness: a comprehensive review of methodologies, bitterants, and influencing factors centered around coffee beverage - Gui-Lin Hu; Jameel Hizam Alafifi; Chen-Xi Quan; Abdulbaset Al-Romaima; Ming-Hua Qiu (Critical Reviews in Food Science and Nutrition, 2025)

Characterization and phylogenetic analysis of the mitochondrial genome of Amatitlania nigrofasciata (Günther, 1867) - Li-Luan Lin; Gui-Feng Wei; Qun Zhang (Journal of Genetics, 2025)

Nonlinear dynamics of rotating graphene-reinforced composite blades under 1:2 internal resonance in fluid-submerged environments - Yi-Han Cheng; Gui-Lin She (Ocean Engineering, 2025)

Clastic record from Northern Tethyan Himalaya: Implication for the initial India-Asian collision in the western Yarlung-Zangpo suture zone, South Tibet - Xu-dong Guo; Lin Ding; Fu-long Cai; Gui-zhen Guo; Xiao-yan Xu; Peng Han; Chang-jun Gu; Mei-yu Liu; Xiang-li Ding; Xu Liu; Xin-lei Li; Deng Zeng; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Active–passive hybrid full-spectrum vibration isolation using tri-stability and cam-roller mechanism - Hong-Fei Chai; Chen Wang; You-Hong Ji; Gui-Lin Wen; Siu-Kai Lai (Engineering Structures, 2025)

Chemical constituents of Rhododendron virgatum Hook and their chemotaxonomic significance - Gui-fang Li; Xin Wang; Hong-ying Chen; Shuai Huang; Lin Chen; Xian-li Zhou (Biochemical Systematics and Ecology, 2025)

Circular RNA hsa_circ_0124644 regulates apoptosis of endothelial cells in coronary artery disease - Ying Cui; Boxin Zhao; Shimeng Wang; Lin Gui; Yingyu Xiang; Zhiyong Zhang; Xueyuan Sun; Jingyao Fan; Jun Liu; Lijuan Huang (In Vitro Cellular & Developmental Biology - Animal, 2025)

Eukaryotic expression and characterization of two α1,2-fucosyltransferase genes in the histo-blood group antigens synthesis pathway of the Pacific oyster (Crassostrea gigas) - Junxia Hu; Meng Qu; Weiran Zhang; Binbin Gui; Yanhua Jiang; Lin Yao; Shixin Wang; Dapeng Wang (Glycoconjugate Journal, 2025)

Investigating antidiabetic drug targets as potential therapeutic modulators for schizophrenia - Yu-Sheng Huang; Xu Lin; Ya-Juan Xu; Gui-Bing Chen (Psychopharmacology, 2025)
Rationale Certain types of antidiabetic drugs (ADs) have been proven to improve cognitive functions and symptom dimensions in schizophrenia (SCZ). Objectives Schizophrenia is a major contributor to social functional impairment, and antipsychotics (APs) remain the cornerstone of its treatment. Investigating the potential of antidiabetic drugs as APs could significantly advance therapeutic strategies for schizophrenia. Methods To assess this potential, we employed an integrated analytical framework that included two-sample Mendelian randomization (MR) using genetic proxies for antidiabetic drug targets, multivariable MR (MVMR), and colocalization analyses. Furthermore, gene and drug enrichment analyses alongside molecular docking studies were performed to elucidate underlying mechanisms and identify candidate drugs. The analysis utilized summary statistics from genome-wide association meta-analyses (GWAS) of schizophrenia, as well as gene expression data from the eQTLGen consortium. Results A total of fourteen drug targets were identified among eight major antidiabetic drugs. Notably, RXRB, a target of thiazolidinediones (TZDs), exhibited a strong inverse association with schizophrenia risk (OR: 0.28, 95% CI: 0.21–0.38, P < 0.001). Other significant targets included GPD1 (targeted by metformin), LRP2 (insulin), SLC5A2 (SGLT2 inhibitors), and ABCC8/KCNJ11 and INS (sulfonylureas). Primary and secondary MR analyses confirmed the associations of RXRB, INS, LRP2, and SLC5A2 with gene expression levels. Drug enrichment and molecular docking analyses identified bezafibrate as a promising candidate for repurposing as an AP. Conclusion Antidiabetic drugs may possess therapeutic potential in schizophrenia by modulating specific drug-related pathways.These findings provide new theoretical support for the selection of ADs in patients with schizophrenia comorbid with diabetes, and also offer new insights for the future development of APs.

Microbial recalcitrant-C metabolism and community composition shifts support enhanced thermal adaptation of soil microbial respiration - Gang Huang; Yan-gui Su; Si-nuo Lin; Zheng-yi Huang; Jin-yi Yan; Xiao-han Dai (Soil Biology and Biochemistry, 2025)

Competitive blockade of NKCC1 by potassium suppresses thallium bioaccumulation and neurotoxicity in zebrafish: Implications for aquatic toxicity - Jian Liu; Xin Li; Yiwen Zhu; Hengyu Gui; Kang Luo; Hongwei Liang; Ai Guan; Weizhen Liu; Hongyu Zhou; Zhang Lin; Bing Yan (Science of The Total Environment, 2025)

Vibration analysis of graphene reinforced metal foam coupled plates under arbitrary boundary and coupled conditions - Bo Zhao; Gui-Lin She (Engineering Structures, 2025)

Photoelectron injection sustains persistent electron-rich Pd for beyond-classical thermocatalytic formic acid dehydrogenation - Xujia Cao; Wenxin Du; Shuai Zhu; Yuan Lin; Yunyun Gui; Lijun Liu (Chemical Engineering Journal, 2025)

Positive effects of gamma aminobutyric acid on growth and lipopolysaccharide-induced intestinal mucosal barrier damage in snakehead (Channa argus) - Xue-qin Wu; Xu-nan Li; Feng-kun Cai; Yun-jie Lin; Xiao-tian Niu; Xiu-mei Chen; Yan-nan Tong; Gui-qin Wang (Aquaculture International, 2025)

Construction of island ecological security pattern under multi-circle development pattern: Evidence from Hainan Island - Sizheng Li; Feng Gui; Hongyu Li; Yanwei Song; Linhao Peng; Lin Zhou; Yang Wang (Ocean & Coastal Management, 2025)

Nutrient availability-driven shifts in nitrogen and phosphorus trade-offs in Microcystis aeruginosa: Understanding cellular resource allocation - Qiang He; Bin Chen; Gui-Jiao Lin; Kai-Kai Deng; Peng Yan; You-Peng Chen; Fang Fang; Jin-Song Guo (Journal of Environmental Management, 2025)

Stepwise recovery of gallium (Ga), lithium (Li), and rare earth elements (REEs) from roasted coal gangue based on leaching kinetics differentiation - Jingzheng Wang; Hongxiang Xu; Yijun Cao; Kejia Ning; Biao Fu; Lin Ma; Xin Sun; Yuntao Kang; Mengting Hong; Guixia Fan; Xiahui Gui; Jiushuai Deng (Hydrometallurgy, 2025)

Molten salt in situ reconstruction realizes ultrafast charge transfer at cobalt-doped-CeO2/CeO2 S-scheme interface for photocatalytic H2O2 production - Yuan Lin; Ziying Feng; Pengjia Li; Shao-Chuan Li; Junhua Zou; Yunyun Gui; Lijun Liu (Chemical Engineering Journal, 2025)

Halogen-sulfur synergy in benzodithiophene-benzodithienedione conjugated polymers: Molecular design of high-performance photoelectrodes for metal anti-corrosion - Rui Ding; Jin-ying Li; Yi-wen Zhang; Hao-han Cao; Xiao Liu; Yu-han Wang; Ming-di Lei; Yu-lin Zhang; An-lan Ji; Yu-chen Zhang; Jie Liu; Tai-jiang Gui; et al. (Chemical Engineering Journal, 2025)

Levonorgestrel-induced anal fin masculinization in mosquitofish: Do TGF-β/BMP signaling and osteogenic remodeling underpin endocrine disruption in aquatic ecosystem? - Weiqian Liang; Tongfu Lu; Dingxian Chen; Weijian Chen; Kaifeng Wang; Jie Lai; Shengyue Lin; Lin Gui; Jian Gong; Chong Han; Qiang Li (Aquatic Toxicology, 2025)

Hyperoside extends lifespan in Caenorhabditis elegans through SEK-1/PMK-1/SKN-1 pathway - Xin-Tian Yu; Lin Shi; Qiong Huang; Bao Li; Yan-Qing Li; Li-Lan Ou; Huai-Rong Luo; Gui-Sheng Wu (Biogerontology, 2025)

Integrin CD11b Alleviates Cerebral Ischemia/Reperfusion Injury via a Mechanism Involving Microglia/Macrophage Polarization - Gui-Nan Jiang; Qiu-Yue Lin; Xiang-Bo An; Wei-Jia Yu; Jie Bai; Xin Yu; Feng Wang; Hui-Hua Li (Journal of Molecular Neuroscience, 2025)

Portable miRNA profiling of sepsis-associated exosomes via a novel DNA molecular lock-mediated nanobiosensor - Wei Xie; Shu Jia; Rongjun Yu; Jianjiang Xue; Shulian Bai; Chenxing Wang; Gang Tian; Qiongyuan Zhang; Xiao Gui; Lilin Wang; Silin Chen; Ke Lin; et al. (Chemical Engineering Journal, 2025)

Ceramifiable flame-retardant silicone rubber foam for long-term fire resistance and thermal insulating - Tao Lin; Ke Shang; Gui-De Lin; Jun-Sheng Wang; Jin-Jun Yang (Chemical Engineering Journal, 2025)

An approach and mechanistic insights of coating-type binders for 4.6 V-LiCoO2 cathode of lithium-ion battery - Li Deng; Yu-Xi Luo; Zhen Wang; Jin-Xia Lin; Jun-Ke Liu; Kun-Gui Zheng; Gao-Yang Bai; Zu-Wei Yin; Yao Zhou; Jun-Tao Li (Chemical Engineering Journal, 2025)

Enhanced Ammonia Nitrogen Removal From Actual Rare Earth Element Tailings Wastewater by Electrocatalytic Oxidation Technology - Yong Zhang; Lingfen Kong; Chen Huang; Shuiyi Lin; Hongjie Gui (Water, Air, & Soil Pollution, 2025)

Establishment and application of environmental geochemical baseline of soil PTEs in a typical metal mining area: a case study of the Xinqiao mining area in Tongling city, Anhui province, China - Jun Zhang; Manli Lin; Herong Gui; Song Chen; Xianghong Liu; Meiping Wu; Xinrui Huang; Li Ma; Weihua Peng (Journal of Soils and Sediments, 2025)

Status of heavy metals contamination in the topsoil of major Oasis cities in Northwest China - Xinlong Xu; Yunfei Liu; Qi Liu; Dongwei Gui; Qian Jin; Sameh Kotb Abd-Elmabod; Tao Lin (Environmental Geochemistry and Health, 2025)

Synthesis of ZIF-8 Coated MnO2 Functionalized Antibacterial Peptide Nanoparticles and Its Antibacterial and Wound-Healing Promotion Studies - Mengzhu Xiao; Yujia Wu; Wanzhen Li; Jun Wang; Weiwei Zhang; Lin Gui; Fei Ge (Current Microbiology, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Simulating vegetation potential and quantifying uncertainty for precision forestation in arid regions - Jia Qu; Zirui Gai; Qi Liu; Dongwei Gui; Xinlong Feng; Jianping Zhao; Tao Lin; Yunfei Liu; Qian Jin; Zeeshan Ahmed (Remote Sensing Applications: Society and Environment, 2025)

Incidence of respiratory diseases associated with per- and polyfluoroalkyl substances (PFAS) in PM2.5: New evidence from a population-based survey of Pearl River Delta (PRD), China - Lu-Yin Wu; Wan-Ting He; Mohammed Zeeshan; Yang Zhou; Yun-Ting Zhang; Li-Xia Liang; Jing-Wen Huang; Jia-Xin Zhou; Kun Zhao; Wen-Wen Bao; Li-Zi Lin; Zhao-Huan Gui; et al. (Journal of Hazardous Materials, 2025)

Passion fruit peel pectin improves glucose and lipid metabolism in high-fat diet-induced obesity through gut microbiota and insulin sensitivity regulation - Ying Ju; Liling Huang; Hailing Luo; Yongcai Huang; Xianya Huang; Ge Chen; Jie Gui; Shengli Lin; Xuzhou Liu; Liu Yang (Food Bioscience, 2025)

SiO2 particles induce pulmonary fibrosis by modulating NLRP3 through the ROS/Keap1/Nrf2 signaling pathway in rats - Shuang Li; Wei-Lei Gong; Lin Liu; Bo Shao; Shun-Li Jiang; Huan Li; Ye Song; Gui-Zhi Han; Zhao-Qiang Zhang (Food and Chemical Toxicology, 2025)

Single-cell sequencing and spatial transcriptomics reveal FAS+ T cell and autophagy-related signatures predicting chemoimmunotherapy response in diffuse large B-cell lymphoma patients - Ning Lou; Liyuan Dai; Ruyun Gao; Jianliang Yang; Lin Gui; Sheng Yang; Peng Liu; Yuankai Shi; Xiaohong Han (Science China Life Sciences, 2025)

Two new species of Russula sect. Heterophyllae (Russulaceae, Russulales) from Jiangxi Province, Eastern China - Lin-Ping Zhang; Li-Hui-Dong Zhao; Xin-Gui Le; Zhen-Wei Mao; Shao-Hua Huang (Mycological Progress, 2025)

Warming exacerbates the effects of pesticides on the soil collembolan gut microbiome and antibiotic resistome - Ya-Ning Wang; Tian-Gui Cai; Ying Li; Wen-Cai Dai; Da Lin; Jin-Ting Zheng; Yi-Fei Wang; Dong Zhu (Journal of Hazardous Materials, 2025)

Genetic and metabolic signatures of blooming-stage tea flowers in novel albino cultivars: Implications for functional food development - Shanshan Zeng; Xiansheng Liao; Zheng Liu; Feng Liu; Wenjing Gui; Weiwei Ren; Hongzheng Lin; Yucheng Zheng; Naixing Ye (Food Bioscience, 2025)

Terpene and lignan glycosides from the leaves of Cyclocarya paliurus and their anti-inflammatory activity - Si-Yang Fang; Jia Liu; Chang-Jian Wu; Xing-Gui Zhang; Hui-Lin Dong; Dong-Jian Zhang; Can Hu; Jian Zhang; Ke Pan; Zhi-Qi Yin; Yan-Hua Qin; Lei Wang (Phytochemistry, 2025)

Fe-doped TiO2 nanosheet exposure accelerates the spread of antibiotic resistance genes by promoting plasmid-mediated conjugative transfer - Ping Cheng; Botao Wang; Qianyu Ji; Pingping Yuan; Shixin Gui; Shuying Liang; Lin Li; Hongwei Xu; Shaoqi Qu (Journal of Hazardous Materials, 2025)

Identifying Novel QTLs and Candidate Genes for Tillering Ability in Sugarcane (Saccharum spp.) - Junteng Fang; Ruiqiang Lai; Zaid Chachar; Yiyun Gui; Lina Fan; Huanzhang Lin; Weijun Cai; Yueping Su; Weiwei Chen; Xiaoming Xue; Yucong Li; Liping Xu; et al. (Sugar Tech, 2025)

Land-use types impact soil ecosystem functions by altering the soil multitrophic biodiversity and interactions - Tian-Lun Zhang; Shao-Yang Zhang; Lu Wang; Da Lin; Bang Ni; Tian-Gui Cai; Shuai Du; Dong Zhu (Soil Ecology Letters, 2025)

The growth performance in different seasons of Homatula variegata (Dabry de Thiersant, 1874) in Northern Guizhou, China - Gui Bang Xiao; Qi Wei Guo; Wei Xi Deng; Qi Qi Xiao; Lin Zhou; Hao Ran Zhang; Jia Lin; Ding Zhi Fang (Journal of Comparative Physiology B, 2025)

A safety and absolute activity measurement method for Phi29 DNA polymerase based on chemiluminescent detection of dATP consumption - Xuefeng Wang; Ping Gui; Xiao Li; Feng Lu; Wei Jing; Changlong Li; Zelin Lu; Yanna Lin; Huancai Yin; Haichao Li; Fuqiang Ma (Analytica Chimica Acta, 2025)

Five racemic phthalides from the aerial parts of Lycopodiastrum casuarinoides and their neuroprotective activities - Yang Liu; Xi Chen; Xue-Jin Liu; Ren Liu; Hui-Ling Hu; Shan-Xue Min; Chao-Hui Huang; Lin Liu; Gui-Shan Tan (Phytochemistry, 2025)

Study on the nitrogen migration of different biomass by activated carbon-based MOF catalyst in hydrothermal environment - Gui-zhong Deng; Xiao-dong Tang; Jing-jing Li; Lin-yu Zhang; Zhi Yang; Fu-xiang Yang (Fuel, 2025)

Chlorinated paraffins exposure in particulate matter increase the risk of attention-deficit/hyperactivity disorder symptoms in children and adolescents - Wan-Ting He; Jing-Wen Huang; Yun-Ting Zhang; Edwin Trevathan; Zhengmin Qian; Ri'enna Boyd; Michael Elliott; Li-Zi Lin; Zhao-Huan Gui; Ru-Qing Liu; Li-Wen Hu; Guang-Hui Dong (Environmental Pollution, 2025)

Reprocessable bio-based rubber with hierarchical hydrogen bonding: A sustainable solution for high strength, superior extensibility, and recyclability - Wei-Chen Zhou; Xue-Qin Gao; Jia-Hao Li; Gui-Lin Hu; Yu-Zhong Wang; Cong Deng (Chemical Engineering Journal, 2025)

An improved U-Pb dating method for carbonates via LA-SF-ICP-MS mapping and its applications - Lili Gui; Xuesong Lu; Fangyue Wang; Can Ge; Lin Jiang; Shaobo Liu; Wuren Xie; Weiyan Chen; Junjia Fan; Hai Wu; Saijun Wu; Yingying Wang; et al. (Science China Earth Sciences, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

A data augmentation method for computer vision task with feature conversion between class - Jiewen Lin; Gui Hu; Jian Chen (Computers and Electronics in Agriculture, 2025)

Greenspace and respiratory diseases and symptoms in Chinese children: A large-scale study exploring joint associations with ozone - Pei-Pei Dong; Gongbo Chen; Yue Wen; Joachim Heinrich; Elaine Fuertes; Tianyu Zhao; Nur Sabrina Idrose; Li-Zi Lin; Zhao-Huan Gui; Xiaodi Qin; Hongwei Tu; Guang-Hui Dong (Sustainable Cities and Society, 2025)

Full realization of the RIBLL2 separator at the HIRFL-CSR facility - Xiao-Dong Xu; Yong Zheng; Zhi-Yu Sun; Yu-Nan Song; Bao-Hua Sun; Satoru Terashima; Chang-Jian Wang; Ge Guo; Guang-Shuai Li; Xiu-Lin Wei; Jun-Yao Xu; Ji-Chao Zhang; et al. (Science Bulletin, 2025)

The association between anthropogenic heat and parent-report symptoms of childhood attention deficit hyperactivity disorder in China: A novel perspective reflecting climate change - Tao Yu; Yue Wen; Pei-Pei Dong; Ming-Kun Sun; Samantha E. Qian; Mario Schootman; Michael G. Vaughn; Shu-Li Xu; He-Hai Huang; Feng-Wen Shan; Shi-Fu Zhu; Jing-Yao Wang; et al. (International Journal of Hygiene and Environmental Health, 2025)

A review: Integration of NIRS and chemometric methods for tea quality control-principles, spectral preprocessing methods, machine learning algorithms, research progress, and future directions - Shengpeng Wang; Clemens Altaner; Lin Feng; Panpan Liu; Zhiyu Song; Luqing Li; Anhui Gui; Xueping Wang; Jingming Ning; Pengcheng Zheng (Food Research International, 2025)

Effect of cultivar and process on the astringency of matcha based on flavonoids-targeted metabolomic analysis - Jinjin Xue; Panpan Liu; Yongquan Xu; Anhui Gui; Xueping Wang; Fei Ye; Lin Feng; Shengpeng Wang; Jing Teng; Shiwei Gao; Pengcheng Zheng (Food Research International, 2025)

Experimental investigation on swelling and gas breakthrough properties of GMZ bentonite considering alkaline solution effects - Lin-Yong Cui; Wei-Min Ye; Qiong Wang; Yong-Gui Chen; Bao Chen; Yu-Jun Cui (Engineering Geology, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Rb2AgBr3:Cu scintillators for high performance gamma and X-ray detection - Qi Wu; Xunsheng Zhou; Wanting Gui; Lu Yao; Yinzhen Wang; Cai Lin Wang (Chemical Engineering Journal, 2025)

A new diterpenoid alkaloid from the Aconitum scaposum - Cheng-En Fu; Gui-Fang Li; Guo-Qing Sun; Shuai Huang; Lin Chen; Xian-Li Zhou (Phytochemistry Letters, 2025)

Deep eutectic solvent-based ultrasonic-assisted extraction of polyphenol from Chenopodium quinoa Willd.: Optimization and lipid-lowering activity - Xiao-tong Lin; Si-xuan Zhou; Zhi-peng Sun; Ming-yuan Cao; Tao Zhou; Li-yan Zhao; Gui-tang Chen (Food Chemistry, 2025)

The key factors of microclimate in courtyard-style architectural ensembles spaces—Taking the Yi minority Tusi manor as an example - Likai Lin; Yan Gui (Building and Environment, 2025)

Effects of fine particulate matter bound heavy metals on intentional self-harm deaths in Guangzhou, China, insight from core chemical constituents - Chunyan Gui; Han Zhang; Zhanlu Lv; Tao Liu; Shengbing Yu; Yanjun Xu; Hualiang Lin; Jianpeng Xiao; Wenjun Ma; Bin Luo; Ling-Chuan Guo (International Journal of Biometeorology, 2025)

Chlorinated paraffins in particulate matter associated with asthma and its relative symptoms in school-aged children and adolescents: A cross-sectional survey in South China - Jing-Wen Huang; Wan-Ting He; Yun-Ting Zhang; Mo Yang; Nan-Xiang Jin; Ari Leskinen; Mika Komppula; Marjut Roponen; Li-Zi Lin; Zhao-Huan Gui; Ru-Qing Liu; Guang-Hui Dong; et al. (Science of The Total Environment, 2025)

High-performance membrane for rapid and selective extraction of uranium from simulated seawater: A novel polyacrylonitrile-poly(amidoxime) hydrogel membrane material - Yunyang Gui; Keze Du; Hao Lin; Xiaoli Su; Fuqiu Ma; Jun Wang; Yun Xue (Journal of Water Process Engineering, 2025)

Environmental life cycle assessment on the recycling processes of power batteries for new energy vehicles - You Zhou; Xue-Dan Cui; Ai-Jun Lin; Yan Dong; Gui-Lan Duan (Journal of Cleaner Production, 2025)

Predicting the efficiency of arsenic immobilization in soils by biochar using machine learning - Jin-Man Cao; Yu-Qian Liu; Yan-Qing Liu; Shu-Dan Xue; Hai-Hong Xiong; Chong-Lin Xu; Qi Xu; Gui-Lan Duan (Journal of Environmental Sciences, 2025)

Microbiome changes and characteristics under nutrient injection for enhanced oil production at Daqing oilfield - Zi-Yue Fu; Wen-Tao Chen; Gui-Na Qi; Zhao-wei Hou; Yi-Fan Liu; Li-Bin Shou; Lei Zhou; Shi-Zhong Yang; Xiao-Lin Wu; Ji-Dong Gu; Bo-Zhong Mu (International Biodeterioration & Biodegradation, 2025)

Nonlinear dynamic response of graphene platelets reinforced cylindrical shells under moving loads considering initial geometric imperfection - Yin-Ping Li; Gui-Lin She (Engineering Structures, 2025)

Association of anthropogenic heat with asthma and related symptoms among children in China: A novel index reflecting climate change - Feng-Wen Shan; Xuan Liu; Ming-Kun Sun; Zhengmin Qian; Michael G. Vaughn; Niraj R. Chavan; Shu-Li Xu; He-Hai Huang; Zhao-Huan Gui; Ru-Qing Liu; Li-Wen Hu; Li-Zi Lin; et al. (Sustainable Cities and Society, 2024)

Outdoor light at night is a modifiable environmental factor for metabolic syndrome: The 33 Communities Chinese Health Study (33CCHS) - Li-Wen Hu; Yan-Chen Gong; Hong-Xing Zou; Le-Bing Wang; Yanan Sun; Alejandro Godinez; Han-Yu Yang; Si-Han Wu; Shuo Zhang; Wen-Zhong Huang; Zhao-Huan Gui; Li-Zi Lin; et al. (Science of The Total Environment, 2024)

Dynamic characteristics of shape-memory alloy plates immersed in liquid subjected to blast loading - Yi-Wen Zhang; Gui-Lin She; M.A. Eltaher (Ocean Engineering, 2024)

A metabolic roadmap of waxy corn flavor - Jingyun Luo; Chunmei He; Shijuan Yan; Chenglin Jiang; An Chen; Kun Li; Yongli Zhu; Songtao Gui; Ning Yang; Yingjie Xiao; Shenshen Wu; Fajun Zhang; et al. (Molecular Plant, 2024)

Phosphorus deficiency promotes root:shoot ratio and carbon accumulation via modulating sucrose utilization in maize - Zu-Dong Xiao; Zhen-Yuan Chen; Yi-Hsuan Lin; Xiao-Gui Liang; Xin Wang; Shou-Bing Huang; Sebastian Munz; Simone Graeff-Hönninger; Si Shen; Shun-Li Zhou (Journal of Plant Physiology, 2024)

Light driven depolymerization of tobacco waste: A multi-scale simulations - Jia-hao Wang; Xian-jie Zhang; Lin-can Fang; Wen-xian Chen; An-Fu Hu; Gui-lin Zhuang (Journal of Environmental Chemical Engineering, 2024)

Muscone inhibits angiotensin II–induced cardiac hypertrophy through the STAT3, MAPK and TGF-β/SMAD signaling pathways - Yi-jiang Liu; Jia-jia Xu; Cui Yang; Yan-lin Li; Min-wei Chen; Shi-xiao Liu; Xiang-hui Zheng; Ping Luo; Rui Li; Di Xiao; Zhong-gui Shan (Molecular Biology Reports, 2024)
Background Muscone is a chemical monomer derived from musk. Although many studies have confirmed the cardioprotective effects of muscone, the effects of muscone on cardiac hypertrophy and its potential mechanisms are unclear.The aim of the present study was to investigate the effect of muscone on angiotensin (Ang) II-induced cardiac hypertrophy. Methods and results In the present study, we found for the first time that muscone exerted inhibitory effects on Ang II-induced cardiac hypertrophy and cardiac injury in mice. Cardiac function was analyzed by echocardiography measurement, and the degree of cardiac fibrosis was determined by the quantitative real-time polymerase chain reaction (qRT-PCR), Masson trichrome staining and western blot assay. Secondly, qRT-PCR experiment showed that muscone attenuated cardiac injury by reducing the secretion of pro-inflammatory cytokines and promoting the secretion of anti-inflammatory cytokines. Moreover, western blot analysis found that muscone exerted cardio-protective effects by inhibiting phosphorylation of key proteins in the STAT3, MAPK and TGF-β/SMAD pathways. In addition, CCK-8 and determination of serum biochemical indexes showed that no significant toxicity or side effects of muscone on normal cells and organs. Conclusions Muscone could attenuate Ang II-induced cardiac hypertrophy, in part, by inhibiting the STAT3, MAPK, and TGF-β/SMAD signaling pathways.

Impacts of February climate conditions in the Gobi Desert on March dust activities in the northern East Asia - Lin Liu; Dongping Bai; Zhili Wang; Deying Wang; Huizheng Che; Yadong Lei; Ke Gui; Junting Zhong; Xiaoye Zhang (Science of The Total Environment, 2024)

Different preferences for inorganic carbon influence CO2 flux under Cyanobacteria or Chlorophyta dominance days - Kai-Kai Deng; Yi-Xuan Li; Peng Yan; Yuan-Chen Huo; Hao Yang; Bin Chen; Qiang He; Gui-Jiao Lin; Jin-Song Guo (Journal of Environmental Management, 2024)

Long-term exposure to ozone and sleep disorders in children: A multicity study in China - Zhao-Huan Gui; Joachim Heinrich; Lidia Morawska; Tian-Yu Zhao; Steve Hung-Lam Yim; Xiang-Qian Lao; Meng Gao; Duo-Hong Chen; Hui-Min Ma; Li-Zi Lin; Ru-Qing Liu; Guang-Hui Dong (Environmental Research, 2024)

Photophysiological status of phytoplankton communities in different types of eddies during winter in the western Pacific Ocean - Jiang Gui; Yingjie Mao; Jun Sun; Mao Lin (Deep Sea Research Part I: Oceanographic Research Papers, 2024)

The long-term effects of norgestrel on the reproductive and thyroid systems in adult zebrafish at environmentally relevant concentrations - Shuyan Mai; Yan-Qiu Liang; Shuhui Zhou; Hongjie Lin; Zhongdian Dong; Chang-Gui Pan; Qingwei Kong; Shaoshuai Wang; Shiqing Wang; Zhong Lin; Liping Hou (Aquatic Toxicology, 2024)

A hybrid genetic tabu search algorithm for distributed job-shop scheduling problems - Jin Xie; Liang Gao; Xinyu Li; Lin Gui (Swarm and Evolutionary Computation, 2024)

Early Cretaceous fayalite-, ferrosilite-, and biotite-bearing rhyolitic porphyries in the Baishuizhai area, South China: Formation by fractional crystallization in the shallow crust - Xiao Liu; Qiang Wang; Xi-Jun Liu; Lin Ma; Derek A. Wyman; Gong-Jian Tang; Wei Dan; Zi-Qi Jiang; Hao Wu; Wan-Long Hu; Jin-Heng Liu; Chuan-Bing Xu; et al. (Lithos, 2024)

Long-term ambient ozone exposure and childhood asthma, rhinitis, eczema, and conjunctivitis: A multi-city study in China - Zhao-Huan Gui; Zhan-Yu Guo; Yang Zhou; Shyamali Dharmage; Lidia Morawska; Joachim Heinrich; Zhang-Kai Cheng; Hui Gan; Zhi-Wei Lin; Dong-Ying Zhang; Jing-Wen Huang; Li-Zi Lin; et al. (Journal of Hazardous Materials, 2024)

Self-Healing fluorinated polymer deep eutectic electrolytes for stable lithium metal batteries - Yingzhi Yu; Canhui Ling; Jixu Yang; Antai Zhu; Tuoya Naren; Yuxin Chen; Yuejiao Chen; Weifeng Wei; Xiaobo Ji; Chengchao Li; Libao Chen; Lin Mei; et al. (Chemical Engineering Journal, 2024)

New terpenoids from Callicarpa nudiflora and their chemotaxonomic significance - Xue-Ying Lin; Gui-Fei Chen; Zi-Xiao Jiang; Yi-Tao Xing; Yang-Yang Liu (Biochemical Systematics and Ecology, 2024)

Tick saliva interference with LTβR signaling facilitates the transmission of Lyme disease spirochetes - Lin Jin; Bao-Gui Jiang; Yizhu Yin; Jingya Guo; Jia-Fu Jiang; Xiaopeng Qi; Gary Crispell; Shahid Karim; Wu-Chun Cao; Ren Lai (Toxicon, 2024)

Long-term exposure to ionic liquid [C8mim]Br induces the potential risk of anxiety and memory deterioration through disturbing neurotransmitter systems - Huangyingzi Wang; Xuhua Li; Jun Li; Fan Yu; Qi Li; Mijia Qin; Lin Gui; Yajie Qian; Manhong Huang (NeuroToxicology, 2024)

Distributions, sea-to-air fluxes, and biological consumption of carbon monoxide in the Bohai and Yellow Seas during winter - Lin Yang; Jiayu Chen; Jing Zhang; Gui-Peng Yang; Bin Yang (Journal of Marine Systems, 2024)

Association between outdoor light at night exposure and executive function in Chinese children - Han-Yu Yang; Si-Han Wu; Shuo Zhang; Hong-Xing Zou; Le-Bing Wang; Li-Zi Lin; Zhao-Huan Gui; Xiao-Wen Zeng; Bo-Yi Yang; Ru-Qing Liu; Guang-Hui Dong; Li-Wen Hu (Environmental Research, 2024)

Nonlinear transient response of rotating graphene platelets reinforced metal foams blades with initial geometric imperfection - Yi-Wen Zhang; Gui-Lin She (Engineering Structures, 2024)

Synergistic structure engineering and electrochemical activation modulating vanadium oxide cathode toward superior zinc-ion storage - Kan Fang; Heng Zhang; Peng Chen; Hua-Yu Zhang; Zhan Wei; Ling Ding; Xiao-Ai Ye; Jiawang Liu; Yi-Lin Liu; Gui-Gen Wang; Hui Ying Yang (Chemical Engineering Journal, 2024)

Strategies to turn adversity into profits: Potential roles of tetrabromobisphenol a and tetrachlorobisphenol a in promoting carbon sequestration and lipid accumulation in microalgae - Bin Chen; Ping Yang; Peng Yan; Gui Jiao Lin; Qiang He; Kai Kai Deng; Jinsong Guo (Chemical Engineering Journal, 2024)

Why does the courtyard spaces of same ethnic group present diverse characteristics in different regions： evidence based on ENVI-met climate modeling - Likai Lin; Yan Gui (Journal of Cleaner Production, 2024)

Emamectin benzoate-induced toxicity affects intestinal epithelial integrity involving apoptosis - Xingyu Yue; Fengxiang Lin; Shuyan Gui; Sai Zhang; Zongbin Wu; Yuxin Xiang; Tianxiang Xiao; Jinjing Xiao; Haiqun Cao; Yanhong Shi (Food and Chemical Toxicology, 2024)

The impact of co-exposure to polystyrene microplastics and norethindrone on gill histology, antioxidant capacity, reproductive system, and gut microbiota in zebrafish (Danio rerio) - Shuhui Zhou; Hongjie Lin; Ziyun Liu; Xiaoyi Lian; Chang-Gui Pan; Zhongdian Dong; Zhong Lin; Chengyong Li; Liping Hou; Yan-Qiu Liang (Aquatic Toxicology, 2024)

Single nucleotide polymorphisms reveal the uniqueness of Gushan semi-rock tea in the tea germplasm resources of Fujian, China - Pan Wang; Shuiyuan Lv; Wentao Yu; Cheng Lin; Yanyu Zhu; Wenjing Gui; Caiguo Liu; Naixing Ye (Genetic Resources and Crop Evolution, 2024)

Spatiotemporal Characteristics of Typical Ecosystem Services and Their Spatial Responses to Driving Factors in Ecologically Fragile Areas in Upper Yellow River, China - Gui Liang; Fengman Fang; Yuesheng Lin; Zhiming Zhang (Chinese Geographical Science, 2024)

Tomato NAC transcription factor NOR-like1 positively regulates tomato fruit softening - Zhen-Zhen Peng; Hong-Li Li; Gang-Shuai Liu; Xiao Su; Xiaodan Zhao; Donald Grierson; Lan-Ting Xiang; Jian-Lin He; Gui-Qin Qu; Hong-Liang Zhu; Ben-Zhong Zhu; Yun-Bo Luo; et al. (Postharvest Biology and Technology, 2024)

Concentrations and influencing factors of 17 elements in placenta, cord blood, and maternal blood of women from an e-waste recycling area - Yacui Luo; Haijun Zhang; Fangzhong Gui; Jiayang Fang; Haijiang Lin; Danhong Qiu; Lingfei Ge; Qiong Wang; Peiwei Xu; Jun Tang (Journal of Trace Elements in Medicine and Biology, 2024)

Structural characteristics of maceral components in exinite-rich coal and their interaction during the direct liquefaction - Jiachen Yu; Lin Lin; Yuanzhe Wang; Zhenyu Liu; Qingya Liu; Xiangen Shan; Huiling Guo; Hezheng Gui; Lei Shi (Fuel, 2024)

Tough and biodegradable C-lignin cross-linked polyvinyl alcohol supramolecular composite films with closed-looping recyclability - Tao Gui; Ling-Ping Xiao; Shuang-Lin Zou; Yue Zhang; Xu Fu; Chang-Hao Liu; Run-Cang Sun (Chemical Engineering Journal, 2024)

The selection of animal models influences the assessment of anti-tumor efficacy: promising sialic acid-conjugate modified liposomes demonstrate remarkable therapeutic effects in diverse mouse strains - Lu Wei; Lin Lin; Jia Wang; Xinying Guan; Wen Li; Yangxu Gui; Shupei Liao; Mingyang Wang; Jiaqi Li; Yihui Deng; Yanzhi Song (Drug Delivery and Translational Research, 2024)

Crenobacter oryzisoli sp. nov., a novel phosphate-solubilizing bacterium isolated from the paddy soil - Shu-Qun Zhang; Cheng-Jie Xie; Ling Yao; Christopher Rensing; Hao Lin; Guo-Hong Liu; Shun-Gui Zhou (Archives of Microbiology, 2024)

A novel approach for sludge deep-dewatering via flowing-out enhancement but not relying on cell lysis and bound water release - Hao Zhang; Wen-Hui Liu; Yun-Yan Gao; Ping Sun; Yuan-Ping Zeng; Lin-Lin Ma; Jiang-Nan Wu; Shun-Gui Zhou; Xi-Qin Cui; Raymond Jianxiong Zeng; Hou-Feng Wang (Water Research, 2024)

Pollution characteristics and prospective risk of microplastics in the Zhengzhou section of Yellow River, China - Fawen Zhang; Zhengyun Deng; Li Ma; Xin Gui; Yuan Yang; Lin Wang; Changmin Zhao; Hetong Li (Science of The Total Environment, 2024)

Intestinal microbiota via NLRP3 inflammasome dependent neuronal pyroptosis mediates anxiety-like behaviour in mice exposed to 3.5 GHz radiofrequency radiation - Gui-qiang Zhou; Xing Wang; Peng Gao; Tong-zhou Qin; Ling Guo; Zhao-wen Zhang; Zhi-fei Huang; Jia-jin Lin; Yun-tao Jing; Hao-nan Wang; Chun-ping Wang; Gui-rong Ding (Science of The Total Environment, 2024)

Produce low-CO2 silica fume hybrid high-strength concrete using dry ice (solid CO2) as a CO2-utilized admixture - Mei-Yu Xuan; Run-Sheng Lin; Yi Han; Gui-yu Zhang; Cheng Guo; Xiao-Yong Wang (Journal of Cleaner Production, 2024)

Climate factors influencing springtime dust activities over Northern East Asia in 2021 and 2023 - Lin Liu; Zhili Wang; Huizheng Che; Deying Wang; Ke Gui; Bo Liu; Kangjie Ma; Xiaoye Zhang (Atmospheric Research, 2024)

CYTOR-NFAT1 feedback loop regulates epithelial-mesenchymal transition of retinal pigment epithelial cells - Rong Zhang; Lin Wang; Yang Li; Yan Liu; Kui Dong; Yajing Pei; Junmei Zhao; Gang Liu; Jing Li; Xiaodan Zhang; Tong Cui; Yan Gao; et al. (Human Cell, 2024)

Positive association between chlorinated paraffins and the risk of allergic diseases in children and adolescents - Jing-Wen Huang; Ya-Ying Bai; Dao-Sen Wang; Wan-Ting He; Jing-Lin Zhang; Hai-Xin Tu; Jing-Yao Wang; Yun-Ting Zhang; Qi-Zhen Wu; Shu-Li Xu; He-Hai Huang; Mo Yang; et al. (Journal of Hazardous Materials, 2024)

Characteristics of energy distribution for N, P and C sequestration by Microcystis aeruginosa under blue and orange light - Dong-ling Long; Gui-jiao Lin; Peng Yan; Hao Yang; Kai-kai Deng; Jin-song Guo (Journal of Environmental Chemical Engineering, 2024)

Ecological and human health hazards of soil heavy metals after wildfire: A case study of Liangshan Yi autonomous prefecture, China - Lin Rao; Chao Zheng; Jian-Bin Chen; Jun-Zhuo Cai; Zhan-Biao Yang; Xiao-Xun Xu; Guo-Chun Lv; Chang-Lian Xu; Gui-Yin Wang; Yu-Bon Man; Ming-Hung Wong; Zhang Cheng (Chemosphere, 2024)

Examination of the effects of triacylglycerol lipase on astaxanthin conversion in the black tiger prawn Penaeus monodon - Xin-Tao Li; Li-Shi Yang; Shi-Gui Jiang; Qi-Bin Yang; Song Jiang; Fa-Lin Zhou; Yun-Dong Li; Jian-Zhi Shi; Xu Chen; Yu-kai Yang; Jian-Hua Huang (Aquaculture, 2024)

Timing of India-Asia suturing: Evidence from a remnant peripheral foreland basin in Xigaze, South Tibet - Xu-Dong Guo; Lin Ding; Qiu-yun Guan; Deng Zeng; Chao Wang; Gui-zhen Guo; Hou-Qi Wang; Mei-Yu Liu; Xiang-Li Ding; Muhammad Qasim; Ya-Hui Yue; Jing Xie; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Systematic identification of wheat spike developmental regulators by integrated multi-omics, transcriptional network, GWAS, and genetic analyses - Xuelei Lin; Yongxin Xu; Dongzhi Wang; Yiman Yang; Xiaoyu Zhang; Xiaomin Bie; Lixuan Gui; Zhongxu Chen; Yiliang Ding; Long Mao; Xueyong Zhang; Fei Lu; et al. (Molecular Plant, 2024)

Combined resonance of graphene platelets reinforced metal foams cylindrical shells with spinning motion under nonlinear forced vibration - Yi-Wen Zhang; Gui-Lin She (Engineering Structures, 2024)

Association of the cloud radiative effect with the changes in the northern edge of Hadley circulation between the CMIP5 and CMIP6 models in boreal summer - Shu Gui; Ruowen Yang; Chuanfeng Zhao; Lin Wang; Jinxin Cheng; Ning Qi; Huan Yang (Theoretical and Applied Climatology, 2024)

The effect of miR-223-3p on endothelial cells in coronary artery disease - Boxin Zhao; Yunhui Zang; Lin Gui; Yingyu Xiang; Zhiyong Zhang; Xueyuan Sun; Jingyao Fan; Lijuan Huang (In Vitro Cellular & Developmental Biology - Animal, 2024)

Effects of dietary betaine supplementation on growth performance, feed intake, intestinal histology, lipid metabolism, and immune response of black tiger shrimp (Penaeus monodon) fed diets containing two levels of raw feed attractants - Gui-Lun He; Meng-Lin Shi; Yu-Cheng Liu; Liu-Tong Chen; Xin Chen; Wen-Bo Zhu; Zheng-Bang Chen; Bei-Ping Tan; Shi-Wei Xie (Aquaculture International, 2024)

Development and evaluation of a bivalent vaccine based on recombinant newcastle disease virus expressing infectious bursal disease virus VP2L-CH3-CH4 in SPF chickens - Wen Ying Sun; Xiao Lin Cao; Yi Xuan Wang; Xiao Chen Guo; Jin Miao Liu; Zhi Qiang Xue; Hui Juan Li; Wei Wang; Ting Ting Zhang; Qianhui Li; Rui Han Qin; Yu Han Jin; et al. (Veterinary Microbiology, 2024)

Generation and origin of persistent high excess pore water pressure in debris flows - Zi-Ming Ye; Ze-Min Xu; Bin Li; Xiao Su; Gui-E Shi; Jing-Kai Meng; Lin Tian (Geomorphology, 2024)

Mechanical-Effect descriptor for oxygen reduction reaction and hydrogen evolution reaction on Single-Atomic Ni-Graphene catalysts - Wei Zhang; Fu-li Sun; Xue-long Zhang; Shuang-te Zhao; Wen-xian Chen; Gui-lin Zhuang (Fuel, 2024)

Global, regional, and national burden of ischemic heart disease attributable to ambient PM2.5 from 1990 to 2019: An analysis for the global burden of disease study 2019 - Li-Hao Guo; Li-Zi Lin; Yang Zhou; Bin Jalaludin; Lidia Morawska; Shyamali C. Dharmage; Luke D. Knibbs; Guo-Feng Huang; Duo-Hong Chen; Huimin Ma; Meng Gao; Joachim Heinrich; et al. (Environmental Research, 2024)

Two calcium-based metal organic frameworks with long afterglow as anticounterfeiting materials - Rong-Hui Shi; Zhi-Qiang Long; Fanan Wang; Ling-Zhu Gong; Xiao-Ying Lin; Gui-Lin Zhuang; Dong-Fei Lu (Chemical Engineering Journal, 2024)

Red blood cell membrane biomimetic nanoprobes for ratiometric imaging of reactive oxygen species level in atherosclerosis - Bo Liu; Gui-Mei Han; Dong-Xia Wang; Ding-Bin Liu; An-An Liu; Jing Wang; Yu-Ling Xiao; Lin Yuan; De-Ming Kong (Chemical Engineering Journal, 2024)

Response of distributions and emissions of summer biogenic sulfur in the Pacific Arctic to enhanced Pacific Water inflow - Cheng‐Xuan Li; Bao‐Dong Wang; Kan Chen; Gui‐Peng Yang; Jian‐Fang Chen; Li‐Na Lin; Zi‐Cheng Wang (Limnology and Oceanography, 2024)
The inflow of warm and nutrient‐rich Pacific Water (PW) through the Bering Strait into the Arctic Ocean is likely to have far‐reaching consequences for the ecosystem and biogenic sulfur cycle in the Earth's sensitive subarctic–arctic region of the Pacific sector, even impacting climate change under global warming scenarios. We performed a detailed biogeochemical study of summer biogenic sulfur cycling from cold (2012) to warm (2014) years in the Bering Strait and the Chukchi Sea, so as to highlight the importance of enhanced Pacific inflow in driving dimethylsulfide (DMS) variability. In the Bering Strait, the enhanced Pacific inflow led to the vertical expansion of the eastern high‐DMS regions due to the vertical extension of Alaska Coastal Water, and the horizontal expansion of the western surface high‐DMS regions due to the westward intrusion of Bering Shelf Water. The enhanced extension of PW potentially stimulated seawater warming, the northward retreat of the ice edge, and the enlargement of sea ice‐free areas in the Chukchi Sea. The northern ice melting zone at 71°N with a bloom of phytoplankton was an area of locally high dimethylsulfoniopropionate concentrations and slow DMS consumption in 2012. A hotspot for dimethylated sulfur compound concentrations and DMS sea–air flux occurred in the convergence region near 67.7°N during 2014, due to enhanced mixing caused by increased Bering Sea Water. Owing to the increased advection of PW during 2012–2014, surface DMS and its emission to the atmosphere increased sharply by threefold in the Chukchi Sea.

Exploring the applications of carbon dioxide radical anion in organic synthesis - Yong-Yuan Gui; Si-Shun Yan; Wei Wang; Lin Chen; Wei Zhang; Jian-Heng Ye; Da-Gang Yu (Science Bulletin, 2023)

Eudesmane-type sesquiterpenoids from the aerial parts of Artemisia lavandulaefolia and their anti-pancreatic cancer activities - Lin-Fen Ding; Guo-Xian Hu; Yu-Yao Liu; Qiu-Hua Wang; Zhang-Juan Li; Meng-Xia Shen; Gui-Fa Zhu; Xing-De Wu; Jia Su (Phytochemistry, 2023)

Two new ketene derivatives from the endophytic fungus Daldinia eschscholtzii J11 - Song-Mei Lu; Cheng-Juan Liao; Yuan Xu; Teng-Yuan Gui; He-Lin Sui; Min Zhou (Phytochemistry Letters, 2023)

Single-cell RNA sequencing reveals a hierarchical transcriptional regulatory network of terpenoid biosynthesis in cotton secretory glandular cells - Jia-Ling Lin; Longxian Chen; Wen-Kai Wu; Xiao-Xiang Guo; Cheng-Hui Yu; Min Xu; Gui-Bin Nie; Jun-ling Dun; Yan Li; Baofu Xu; Ling-Jian Wang; Xiao-Ya Chen; et al. (Molecular Plant, 2023)

Enhanced photocatalytic performance of Mn-doped CeO2 nanoribbons for VOCs degradation: Investigating charge rearrangement and local electric field effects - Ying Wang; Yuan Lin; Jianhua Zhang; Yunyun Gui; Lijun Liu (Journal of Environmental Chemical Engineering, 2023)

An acidic heteropolysaccharide rich in galactose and arabinose derived from ginger: Structure and dynamics - Xiao-tong Lin; Bo-xian Xiao; Jun-ping Liu; Ming-yuan Cao; Zhi-ping Yang; Li-yan Zhao; Gui-tang Chen (Food Bioscience, 2023)

Spatial bandgap tailoring via a novel injection chemical bath deposition enables highly efficient carbon-based Sb2(S,Se)3 thin film solar cells - Peng Tang; Zi-Heng Huang; You-Xian Chen; Hu Li; Li-Quan Yao; Hui Li; Li-Mei Lin; Jin-Rui Cai; Ya-Lu Zhan; Dong Wei; Shui-Yuan Chen; Da-Qin Chen; et al. (Chemical Engineering Journal, 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

Inspiration or perspiration: Diffusion of China's low-carbon city pilot policies nationwide - Xiang Luo; Guodong Lin; Qing Wan; Gui Jin (Journal of Cleaner Production, 2023)

Health risk assessment of trace metal(loid)s in agricultural soil using an integrated model combining soil-related and plants-accumulation exposures: A case study on Hainan Island, South China - Bi-gui Lin; Pan Pan; Chao-xian Wei; Xi-chao Chen; Zong-yao Zhang; Qing-fang Fan; Fang Liu; Bei-bei Liu; Lin Wu (Science of The Total Environment, 2023)

Impact of bentonite on greenhouse gas emissions during pig manure composting and its subsequent application - Jia-Ping Wu; Meng-Ling Li; Yan Wang; Shan Lin; Rong-Gui Hu; Rong-Biao Xiang (Journal of Environmental Management, 2023)

The effect of glycerol additive on high value-added chemicals from tobacco waste pyrolysis - Jia-hao Wang; Xian-jie Zhang; Qian Xia; Shui yang Fang; An-fu Hu; Jun Wen; Sheng-jun Zhou; Wen-xian Chen; Gui-lin Zhuang (Journal of Environmental Chemical Engineering, 2023)

Advanced electrooxidation of florfenicol using 3D printed Nb2O5/Ti electrodes: Degradation efficiency, dehalogenation performance, and toxicity reduction - Yun-fei Zhang; Jia-le Gao; Shen-gui Chen; Lei Li; Jian-hui Xu; Dan Li; Yu-feng Liu; Xin Quan; Xin Fu; Ya-zi Xie; Jing-nan Wu; Dan-ying Lin; et al. (Chemical Engineering Journal, 2023)

Unlocking interfacial dynamics of biocompatible MXene/polyurethane-based nanocomposites for photothermal de-icing and thermal safety - Tianyang Cui; Wei Cai; Yapeng Zheng; Jingwen Wang; Bicheng Lin; Zhou Gui; Jixin Zhu (Chemical Engineering Journal, 2023)

Ketamine exerts dual effects on the apoptosis of primary cultured hippocampal neurons from fetal rats in vitro - Guo-Hua Wu; Que-Hui Guo; Xiao-Dong Xu; Jian-Chang Lin; Gui-Ting You; Cai-Hou Lin; Liang-Cheng Zhang (Metabolic Brain Disease, 2023)

Identification of Genes Related to Resistance to Ichthyophthirius multifiliis Based on Co-expression Network Analysis in Grass Carp - Feng Chen; Wei Zhang; Xiaoyan Xu; Lang Gui; Yanfeng Lin; Minglin Wu; Jiale Li; Yubang Shen (Marine Biotechnology, 2023)

Drynaria Naringin alleviated mechanical stress deficiency-caused bone loss deterioration via Rspo1/Lgr4-mediated Wnt/β-catenin signalling pathway - Gui-Xun Shi; Wei-Dong Sun; Zeng-Huan Chen; Chuan-Jun Yang; Wang-Lin Luo; Dan-Feng Wang; Ze-Zhu Zhou (In Vitro Cellular & Developmental Biology - Animal, 2023)

Isolation and characterization of 32 SNP markers in Spinibarbus hollandi based on restriction site-associated DNA sequencing (RADseq) - Wenwei Huang; Jiangwei Zhou; Huawei Zhan; Yuying Zhang; Suhan Peng; Wenjun Li; Zusheng Yi; Lin Gui; Chong Han; Qiang Li (Conservation Genetics Resources, 2023)

Mitochondrial RNA m3C methyltransferase METTL8 relies on an isoform-specific N-terminal extension and modifies multiple heterogenous tRNAs - Meng-Han Huang; Jin-Tao Wang; Jian-Hui Zhang; Xue-Ling Mao; Gui-Xin Peng; Xiuying Lin; Daizhu Lv; Chen Yuan; Huan Lin; En-Duo Wang; Xiao-Long Zhou (Science Bulletin, 2023)

Effects of filter cartridge wetted before filtration and during filtration on the performance of cartridge dust collector - Shihang Li; Liyuan Liu; Xiaoyu Tan; Hao Liu; Changgeng Gui; Xingyue Chen; Muze Han; Yihan Lin; Jiang Shao; Liang Yuan; Fubao Zhou (Process Safety and Environmental Protection, 2023)

Continuous extensional uplift controls the Silurian structural evolution of the Sichuan Basin, southwest China - Gen Li; Zhong-Quan Li; Dian Li; Heng-Lin Liu; Shan Yan; Gui-Ping Su; Xing-Wang Tian (Marine and Petroleum Geology, 2023)

The association between childhood adiposity in northeast China and anthropogenic heat flux: A new insight into the comprehensive impact of human activities - Hong-Zhi Zhang; Dao-Sen Wang; Si-Han Wu; Guo-Feng Huang; Duo-Hong Chen; Hui-Min Ma; Yun-Ting Zhang; Li-Hao Guo; Li-Zi Lin; Zhao-Huan Gui; Ru-Qing Liu; Li-Wen Hu; et al. (International Journal of Hygiene and Environmental Health, 2023)

Novel hydrocortisone magnetic molecularly imprinted polymers: Preparation, characterization, and application - Si-xuan Zhou; Xiao-tong Lin; Jie Wang; Hai-xiang Wang; Gui-tang Chen (Food Chemistry, 2023)

Characterization of the vertical evolution of urban nocturnal boundary layer by UAV measurements: Insights into relations to cloud radiative effect - Lin Shen; Jiaoshi Zhang; Yin Cheng; Xiaofeng Lu; Haosheng Dai; Dexia Wu; Da-Ren Chen; Jianguo Liu; Huaqiao Gui (Environmental Research, 2023)

A model for describing advective and diffusive gas transport through initially saturated bentonite with consideration of temperature - Lin-Yong Cui; Wei-Min Ye; Qiong Wang; Yong-Gui Chen; Yu-Jun Cui (Engineering Geology, 2023)

Over-expression of miR-3584-5p Represses Nav1.8 Channel Aggravating Neuropathic Pain caused by Chronic Constriction Injury - Ran Yang; Qian-qian Wang; Yuan Feng; Xue-hao Li; Gui-xia Li; Feng-lin She; Xi-jin Zhu; Chun-li Li (Molecular Neurobiology, 2023)

The associations of non-essential metal mixture with fasting plasma glucose among Chinese older adults without diabetes - Jing-Yuan Lei; Pan-Pan Wang; Hong-Li Wang; Yuan Wang; Liang Sun; Bing Hu; Su-Fang Wang; Dong-Mei Zhang; Gui-Mei Chen; Chun-Mei Liang; Fang-Biao Tao; Lin-Sheng Yang; et al. (Environmental Science and Pollution Research, 2023)

First transcriptome profiling in gill and hepatopancrease tissues of Metapenaeus ensis in response to acute ammonia-N stress - Yun-Dong Li; Meng-Ru Si; Shi-Gui Jiang; Qi-Bin Yang; Song Jiang; Li-Shi Yang; Jian-Hua Huang; Fa-Lin Zhou (Fish & Shellfish Immunology, 2023)

TRPC6 promotes daunorubicin-induced mitochondrial fission and cell death in rat cardiomyocytes with the involvement of ERK1/2-DRP1 activation - Li-Xia Xu; Rui-Xing Wang; Jian-Feng Jiang; Gao-Cheng Yi; Jin-Jin Chang; Rui-Lan He; Hai-Xia Jiao; Bin Zheng; Long-Xin Gui; Jun-Jin Lin; Zhi-Hong Huang; Mo-Jun Lin; et al. (Toxicology and Applied Pharmacology, 2023)

A new sesquiterpene synthase catalyzing the formation of (R)-β-bisabolene from medicinal plant Colquhounia coccinea var. mollis and its anti-adipogenic and antibacterial activities - De-Sen Li; Lin-Lin Shi; Kai Guo; Shi-Hong Luo; Yan-Chun Liu; Yue-Gui Chen; Yan Liu; Sheng-Hong Li (Phytochemistry, 2023)

A clean two-stage Bayer process for achieving near-zero waste discharge from high-iron gibbsitic bauxite - Guo-tao Zhou; Yi-lin Wang; Yu-guan Zhang; Tian-gui Qi; Qiu-sheng Zhou; Gui-hua Liu; Zhi-hong Peng; Xiao-bin Li (Journal of Cleaner Production, 2023)

Rational design of one inorganic-organic hybrid Z-scheme heterojunction for high-performance photocatalytic water splitting - Cun-biao Lin; Fu-li Sun; Jun Wen; Wen-xian Chen; Gui-lin Zhuang (Fuel, 2023)

Toward sustainable green alumina production: A critical review on process discharge reduction from gibbsitic bauxite and large-scale applications of red mud - Guo-tao Zhou; Yi-lin Wang; Tian-gui Qi; Qiu-sheng Zhou; Gui-hua Liu; Zhi-hong Peng; Xiao-bin Li (Journal of Environmental Chemical Engineering, 2023)

Surface engineering AgNW transparent conductive films for triboelectric nanogenerator and self-powered pressure sensor - Yanqiang Lei; Jiahong Yang; Yao Xiong; Shishuo Wu; Weidong Guo; Gui-Shi Liu; Qijun Sun; Zhong Lin Wang (Chemical Engineering Journal, 2023)

Interaction Between the Glymphatic System and α-Synuclein in Parkinson’s Disease - Yu Zhang; Cui Zhang; Xu-Zhong He; Zhen-Hua Li; Jing-Cai Meng; Rui-Ting Mao; Xin Li; Rong Xue; Qian Gui; Guo-Xing Zhang; Lin-Hui Wang (Molecular Neurobiology, 2023)

The law of strength damage and deterioration of jointed sandstone after dry-wet cycles - Gui-lin Wang; Tian-yu Zhang; Liang Zhang (Journal of Mountain Science, 2023)

A novel l-rhamnose-binding lectin participates in defending against bacterial infection in zebrafish - Jing Wang; Xin-Lu Guo; Hong-Ye Chen; Lin-Xi Xiao; Gui-Wen Yang; Hui-Ting Yang (Fish & Shellfish Immunology, 2023)

Sex difference on fibroblast growth factors (FGFs) expression in skin and wound of streptozotocin(STZ)-induced type 1 diabetic mice - Nuo-qi Wang; Wei-hua Jia; Lin Yin; Na Li; Mei-dai Liang; Jia-min Shang; Bi-yu Hou; Li Zhang; Gui-fen Qiang; Guan-hua Du; Xiu-ying Yang (Molecular Biology Reports, 2023)

Nicosulfuron stress on the glyoxalase system and endogenous hormone content in sweet maize seedlings - Zhen-Xing Wu; Jian Wang; Xiao-Hu Lin; Qing Yang; Ting-Zhen Wang; Jian-Jian Chen; Xiang-Nan Li; Yuan Guan; Gui-Hua Lv (Environmental Science and Pollution Research, 2023)

A rational design of functionalized black phosphorus cooperates with piperazine pyrophosphate to significantly suppress the fire hazards of polypropylene - Wei Liu; Longlong Ding; Lin Wang; Congwu Zhang; Weiye Yang; Dongli Liu; Zhou Gui; Weizhao Hu (Chemosphere, 2023)

Screening and characterization of sex-specific markers by NGS sequencing in Spinibarbus hollandi with implication of XY sex determination system - Chong Han; Wenwei Huang; Suhan Peng; Jiangwei Zhou; Huawei Zhan; Lin Gui; Wenjun Li; Qiang Li (Aquaculture, 2023)

Ecological value of mariculture shellfish resources in China: Assessment and management - Chun-Yu Lin; Gui-Lin Dai; Yang Liu; Meng-Qi Zhang; Ying Liu; Wen Jiang; Xiu-Mei Fu; Han-Xue Chen (Marine Policy, 2023)

FSP synthesized core-shell CuOx@SiO2 catalyst with excellent thermal stability for catalytic combustion of ammonia - Guangzhao Zhou; Yiran Zhang; Xuteng Zhao; Yu Gui; Xiaochao Wang; Linjia Li; Ting Chen; Zhen Huang; He Lin (Fuel, 2023)

Patterns of organic carbon and nitrogen stocks in soil particle-size fractions along an aridity gradient in Northern China’s deserts - Yan-gui Su; Gang Huang; Si-nuo Lin; Zheng-yi Huang; Guo-peng Wu; Hao Cheng (CATENA, 2023)

Phosphorus availability mediates plant–plant interaction and field productivity in maize-grass pea intercropping system: Field experiment and its global validation - Shuang-Guo Zhu; Hong-Yan Tao; Wen-Bo Li; Rui Zhou; Yan-Wen Gui; Li Zhu; Xiao-Lin Zhang; Wei Wang; Bao-Zhong Wang; Fu-Jian Mei; Hao Zhu; You-Cai Xiong (Agricultural Systems, 2023)

Within-species plant phylogeny drives ectomycorrhizal fungal community composition in tree roots along a timberline - Teng Yang; Luyao Song; Han-Yang Lin; Ke Dong; Xiao Fu; Gui-Feng Gao; Jonathan M. Adams; Haiyan Chu (Soil Biology and Biochemistry, 2023)

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

Occurrence, controlling factors and noncarcinogenic risk assessment based on Monte Carlo simulation of fluoride in mid-layer groundwater of Huaibei mining area, North China - Huili Qiu; Herong Gui; Haifeng Xu; Lin Cui; Hao Yu (Science of The Total Environment, 2023)

Fine chemical speciation and environmental impact capacity of trace elements with different enrichment levels in coal - Yuan Liu; Yong Wei; Guijian Liu; Biao Fu; Bingyu Chen; Jiamei Zhang; Lin Gui; Huihui Zhou; Muyuan Lu (Science of The Total Environment, 2023)

Contrast the distribution, transformation, and degradation of dissolved and particulate organic matter in the South Yellow Sea, the East China Sea, and its adjacent Kuroshio Current - Chong-Xiao Ji; Gui-Peng Yang; Yan Chen; Zhen He; Yan Li; Lin Zhang (Marine Chemistry, 2023)

Assessment of algae and greenhouse gases in different reservoirs worldwide by reactor model - Yi-Xuan Li; Kai-Kai Deng; Shu-Qing Zhang; Gui-Jiao Lin; Fang Fang; Jin-Song Guo (Journal of Cleaner Production, 2023)

Effects of physiologic activities of plankton on CO2 flux in the Three Gorges Reservoir after rainfall during algal blooms - Yi-Xuan Li; Kai-Kai Deng; Gui-Jiao Lin; Bin Chen; Fang Fang; Jin-Song Guo (Environmental Research, 2023)

Acinetobacter faecalis Sp. Nov., Isolated from Elephant Faeces - Xue-Mei Chen; De-Feng An; Si-Rong He; Shao-Juan Yang; Zu-Zhen Yang; Lian-Shuang Xiong; Gui-Ding Li; Ming-Guo Jiang; Cheng-Lin Jiang; Yi Jiang (Current Microbiology, 2023)

Selenium attenuates the association of co-exposure to arsenic, cadmium, and lead with cognitive function among Chinese community-dwelling older adults - Bei-Jing Cheng; Jie Sheng; Hong-Li Wang; Yuan Wang; Hong-Juan Cao; Xiu-De Li; Ting-Ting Zhou; Xiang-Long Meng; Huan-Huan Nie; Su-Fang Wang; Dong-Mei Zhang; Gui-Mei Chen; et al. (Environmental Science and Pollution Research, 2022)

The association between essential trace element mixture and atherosclerotic cardiovascular disease risk among Chinese community-dwelling older adults - Xiang-long Meng; Yuan Wang; Hong-li Wang; Huan-huan Nie; Bei-jing Cheng; Hong-juan Cao; Xiu-de Li; Su-fang Wang; Gui-mei Chen; Fang-biao Tao; Jie Sheng; Lin-sheng Yang (Environmental Science and Pollution Research, 2022)

Climatology of aerosol types and their vertical distribution over East Asia based on CALIPSO lidar measurements - Lu Gui; Minghui Tao; Yi Wang; Lunche Wang; Liangfu Chen; Changqing Lin; Jinhua Tao; Jun Wang; Chao Yu (International Journal of Climatology, 2022)
Aerosol vertical distribution generally determines their health impacts and climate effects. By using long‐term (2007–2019) CALIPSO lidar measurements, we present a large‐scale insight into the climatology of aerosol types and their vertical structure over East Asia. Despite the low sampling frequency, comparison with MODIS aerosol optical depth (AOD) shows that the integrated CAIPSO vertical extinction can reasonably reproduce spatial patterns of the aerosol loading. With the unique advantage of active detection, CALIPSO reveals an obvious enhancement of the night‐time AOD due to worse diffusion conditions. Moreover, long‐range transport of different aerosols including dust, polluted dust, and smoke has substantial contribution to the aerosol loading over East Asia. Pure dust particles are mainly concentrated over the deserts with notable dust transport belts (dust AOD > 0.2 at 532 nm) along downwind regions during winter and spring. By contrast, polluted dust is prevalent over the downstream eastern China with much higher AODs throughout the year. In particular, AOD of polluted dust (~0.5) is higher in winter rather than in spring, which is consistent with their seasonal occurrences. Smoke aerosols usually appear in the night‐time over southern China. The top heights of aerosols are around 4–6 km, with dust and smoke having higher extinction at upstream regions. The climatology of these aerosol types and vertical distribution can provide a significant constraint for associated studies of air quality and climate effects.

Genetic Diversity Evaluation and Population Structure Analysis of Red Swamp Crayfish (Procambarus clarkii) from Lakes and Rice Fields by SSR Markers - Xin-Fen Guo; Min Liu; Yu-Lin Zhou; Wen-Yu Wei; Zhi Li; Li Zhou; Zhong-Wei Wang; Jian-Fang Gui (Fishes, 2022)
The red swamp crayfish (Procambarus clarkii) is an important aquatic animal and has developed as a popular aquaculture species in China. In this study, a total of 72,839 SSR motifs were identified from transcriptional data, and 20 microsatellite markers of them were finally developed to assess the genetic diversities of seven wild populations from natural lakes and nine cultured populations from rice fields. Genetic diversity was slightly higher in the cultured populations than in the wild populations. The degree of genetic differentiation between cultured populations is slight, while a moderate to a large degree of genetic differentiation between wild populations and most of the variations occurred within individuals (79%). The analysis of cluster, principal coordinate analysis and STRUCTURE were similar, and they showed that isolation-by-distance pattern was not significant. The microsatellite markers developed in this study can not only be used for genetic monitoring of population but also provide important information for the management of breeding and cultured population in red swamp crayfish.

Characterization of Joint Roughness Heterogeneity and Its Application in Representative Sample Investigations - Shi-Gui Du; Hang Lin; Rui Yong; Guang-Jian Liu (Rock Mechanics and Rock Engineering, 2022)
Rock joint surface roughness is usually characterized by heterogeneity, but the determination of a required number of samples for achieving a reasonable heterogeneity assessment remains a challenge. In this paper, a novel method, the global search method, was proposed to investigate the heterogeneity of rock joint roughness. In this method, the roughness heterogeneity was characterized based on a statistical analysis of the roughness of all samples extracted from different locations of a given rock joint. Analyses of the effective sample number were conducted, which showed that sampling bias was caused by an inadequate number of samples. To overcome this drawback, a large natural slate joint sample (1000 mm × 1000 mm in size) was digitized in a laboratory using a high-accuracy laser scanner. The roughness heterogeneities of both two-dimensional (2D) profiles and three-dimensional (3D) surface topographies were systematically investigated. The results show that the expected value obtained from conventional methods failed to accurately represent the overall roughness. The relative errors between the population parameter and the expected value varied not only from sample to sample but also with the scale. The roughness heterogeneity characteristics of joint samples of various sizes can be obtained using the global search method. This new method could facilitate the determination of the most representative samples and their positions.

First report of chilli veinal mottle virus infecting tobacco in Guizhou, China - Yue Chen; Ting Ting Li; Jing Zhong; Li Ling Zhao; Ya Li Guo; Ye Chun Lin; Gui Gao; Yi Cao; Ming Ding (Journal of Plant Pathology, 2022)

Responses of photosynthesis, antioxidant enzymes, and related gene expression to nicosulfuron stress in sweet maize (Zea mays L.) - Zhen-Xing Wu; Ning-Wei Xu; Min Yang; Xiang-Ling Li; Jin-Ling Han; Xiao-Hu Lin; Qing Yang; Gui-Hua Lv; Jian Wang (Environmental Science and Pollution Research, 2022)

Identification and expression profiling of HSP20 genes in Neoporphyra haitanensis - Ling-Na Peng; Lin-Bin Huang; Tian-Yu Gui; Da-Hai Gao; Xing-Hong Yan (Journal of Applied Phycology, 2022)

Synthesis, antifungal activity and 3D-QSAR study of novel acyl thiourea compounds containing gem-dimethylcyclopropane ring - Mei Huang; Min Huang; Xiu Wang; Wen-Gui Duan; Gui-Shan Lin; Fu-Hou Lei (Molecular Diversity, 2022)

Celastrol attenuates chronic constrictive injury-induced neuropathic pain and inhibits the TLR4/NF-κB signaling pathway in the spinal cord - Gui-juan Jin; Xuehuizi Peng; Zhi-Guo Chen; Yu-lin Wang; Wen-jun Liao (Journal of Natural Medicines, 2022)

Nakamurella leprariae sp. nov., isolated from a lichen sample - De-Feng An; Shao-Juan Yang; Long-Qian Jiang; Xin-Yu Wang; Xiao-Yu Huang; Lei Lang; Xue-Mei Chen; Ming-Qun Fan; Gui-Ding Li; Ming-Guo Jiang; Li-Song Wang; Cheng-Lin Jiang; et al. (Archives of Microbiology, 2022)

Streptomyces blattellae, a novel actinomycete isolated from the in vivo of a Blattella germanica - Gui-Min Liu; Lin-Lin Yuan; Li-Li Zhang; Hong Zeng (Antonie van Leeuwenhoek, 2022)

A dice similarity measure for TBM penetrability classification in hard rock condition with the intuitionistic fuzzy information of rock mass properties - Rui Yong; Jun Ye; Shi-Gui Du; He Zhang; Leiyu Gu; Hang Lin (European Journal of Environmental and Civil Engineering, 2021)

Euphanoids A and B, two new lathyrane diterpenoids with nitric oxide (NO) inhibitory activity from Euphorbia kansuensis - Xue-Long Yan; Run-Zhu Fan; Jun Sang; Xing-Lin Xie; Gui-Hua Tang; Sheng Yin (Natural Product Research, 2021)

Application of hydrogen-rich water modulates physio-biochemical functions and early growth of fragrant rice under Cd and Pb stress - Lin Ma; Leilei Kong; Runfei Gui; Xiaojuan Yang; Jianwen Zhang; Qi Gong; Dejun Qin; Maosen Zhuang; Umair Ashraf; Zhaowen Mo (Environmental Science and Pollution Research, 2021)

Synthesis and biological evaluation of novel 1,3-diphenylurea quinoxaline derivatives as potent anticancer agents - Gui-Zhen Li; Xi-Lin Ouyang; Zu-Yu Mo; Yao Gu; Xiao-Lin Cao; Li Yang; Hai-Tao Tang; Ying-Ming Pan (Medicinal Chemistry Research, 2021)

The developmental regulator PatD modulates assembly of the cell‐division protein FtsZ in the cyanobacterium Anabaena sp. PCC 7120 - Li Wang; Tian‐Cai Niu; Ana Valladares; Gui‐Ming Lin; Ju‐Yuan Zhang; Antonia Herrero; Wen‐Li Chen; Cheng‐Cai Zhang (Environmental Microbiology, 2021)
Summary FtsZ is a tubulin‐like GTPase that polymerizes to initiate the process of cell division in bacteria. Heterocysts are terminally differentiated cells of filamentous cyanobacteria that have lost the capacity for cell division and in which the ftsZ gene is downregulated. However, mechanisms of FtsZ regulation during heterocyst differentiation have been scarcely investigated. The patD gene is NtcA dependent and involved in the optimization of heterocyst frequency in Anabaena sp. PCC 7120. Here, we report that the inactivation of patD caused the formation of multiple FtsZ‐rings in vegetative cells, cell enlargement, and the retention of peptidoglycan synthesis activity in heterocysts, whereas its ectopic expression resulted in aberrant FtsZ polymerization and cell division. PatD interacted with FtsZ, increased FtsZ precipitation in sedimentation assays, and promoted the formation of thick straight FtsZ bundles that differ from the toroidal aggregates formed by FtsZ alone. These results suggest that in the differentiating heterocysts, PatD interferes with the assembly of FtsZ. We propose that in Anabaena FtsZ is a bifunctional protein involved in both vegetative cell division and regulation of heterocyst differentiation. In the differentiating cells PatD‐FtsZ interactions appear to set an FtsZ activity that is insufficient for cell division but optimal to foster differentiation.

Glaciibacter flavus sp. nov., isolated from a lichen sample - De-Feng An; Long-Qian Jiang; Kun Zhang; Gui-Ding Li; Xin-Yu Wang; Ming-Guo Jiang; Lei Lang; Li-Song Wang; Johannes F. Imhoff; Cheng-Lin Jiang; Yi Jiang (Archives of Microbiology, 2021)

Different posterior hippocampus and default mode network modulation in young APOE ε4 carriers: a functional connectome-informed phenotype longitudinal study - Li Juan Zheng; Li Lin; U. Joseph Schoepf; Akos Varga-Szemes; Rock H. Savage; Han Zhang; Yun Fei Wang; Xin Yuan Zhang; Song Luo; Ya Liu; Gui Fen Yang; Guang Ming Lu; et al. (Molecular Neurobiology, 2021)

Paracoccus lichenicola sp. nov., Isolated from Lichen - Lei Lang; De-Feng An; Long-Qian Jiang; Gui-Ding Li; Li-Song Wang; Xin-Yu Wang; Qin-Yuan Li; Cheng-Lin Jiang; Yi Jiang (Current Microbiology, 2021)

Experimental evidence for long‐term coexistence of copiotrophic and oligotrophic bacteria in pelagic surface seawater - Yi Li; Zhi‐Bin Wang; Xi‐Ying Zhang; Yan‐Ru Dang; Lin‐Lin Sun; Wei‐Peng Zhang; Hui‐Hui Fu; Gui‐Peng Yang; Min Wang; Andrew McMinn; Xiu‐Lan Chen; Yin Chen; et al. (Environmental Microbiology, 2021)
Summary Most marine copiotrophic bacteria can produce extracellular enzymes to degrade biopolymers into bio‐available smaller solutes, while oligotrophic bacteria usually cannot. Bacterial extracellular enzymes and enzymatic products can be a common resource that could be utilized by both copiotrophs and oligotrophs; when present, oligotrophs may outcompete the enzyme‐producing copiotrophs. However, copiotrophs and oligotrophs consistently coexist in the ocean. How they maintain coexistence has still not been experimentally studied. In this study, the interaction and coexistence of a copiotroph and an oligotroph, isolated from the same surface seawater sample and utilizing the same proteinaceous substrate, were experimentally investigated. The copiotroph could secrete extracellular proteases to degrade and then utilize the proteinaceous substrate. The oligotroph was unable to utilize the proteinaceous substrate by itself, but could grow by using the hydrolysate amino acids. The copiotroph outcompeted the oligotroph by adsorbing the amino acids quickly and having a higher growth rate in the rich medium. The oligotroph survived by adapting to low concentration of nutrients. The copiotroph and oligotroph were able to maintain long‐term (up to 142 days) coexistence in the laboratory. This study indicates that differences in the utilization of different concentrations of nutrients can drive the coexistence of marine copiotrophs and oligotrophs.

Tectochrysin increases stress resistance and extends the lifespan of Caenorhabditis elegans via FOXO/DAF-16 - Min Lu; Lin Tan; Xiao-Gang Zhou; Zhong-Lin Yang; Qing Zhu; Jian-Ning Chen; Huai-Rong Luo; Gui-Sheng Wu (Biogerontology, 2020)

Comparative analysis and natural evolution of squalene epoxidase in three Fritillaria species - Xu Lu; Lin-Ning Zhang; Jin-Fa Du; Xiao-Yan Zheng; Hui-Jun Li; Ping Li; Gui-Zhong Xin; Yan Jiang (Plant Molecular Biology, 2020)

Two novel pleiotropic loci associated with osteoporosis and abdominal obesity - Lu Liu; Xiao-Lin Yang; Hong Zhang; Zi-Jia Zhang; Xin-Tong Wei; Gui-Juan Feng; Ju Liu; Hui-Ping Peng; Rong Hai; Hui Shen; Qing Tian; Hong-Wen Deng; et al. (Human Genetics, 2020)

Enhancement of the activity of Cu/TiO2 catalyst by Eu modification for selective catalytic reduction of NOx with NH3 - Yuan-zhen Liu; Qi-yan Xu; Rui-tang Guo; Chao-peng Duan; Gui-lin Wu; Yu-fang Miao; Jing-wen Gu (Environmental Science and Pollution Research, 2020)

Nakamurella albus sp. nov.: A Novel Actinobacterium Isolated from a Lichen Sample - Long-Qian Jiang; De-Feng An; Kun Zhang; Gui-Ding Li; Xin-Yu Wang; Lei Lang; Ming-Guo Jiang; Li-Song Wang; Cheng-Lin Jiang; Yi Jiang (Current Microbiology, 2020)

Selective catalytic reduction of NOx by NH3 over CeVO4-CeO2 nanocomposite - Chao-peng Duan; Rui-tang Guo; Gui-lin Wu; Wei-guo Pan (Environmental Science and Pollution Research, 2020)

Influence of Aphis gossypii feeding on defense strategy of native and introduced populations of Ageratina adenophora - Ying Lin; Shu-Qi He; Zhi-Hui Lu; Yu-Lin Gao; Yan-Ru Duan; Zheng-Yue Li; Bin Chen; Fu-Rong Gui (Arthropod-Plant Interactions, 2020)

Liver X receptor activation induces podocyte injury via inhibiting autophagic activity - Ziyi Zhang; Shengjie Tang; Weiwei Gui; Xihua Lin; Fenping Zheng; Fang Wu; Hong Li (Journal of Physiology and Biochemistry, 2020)

Immunogenicity noninferiority study of 2 doses and 3 doses of an Escherichia coli-produced HPV bivalent vaccine in girls vs. 3 doses in young women - Yue-Mei Hu; Meng Guo; Chang-Gui Li; Kai Chu; Wen-Gang He; Jing Zhang; Jian-Xiang Gu; Juan Li; Hui Zhao; Xiang-Hong Wu; BiZhen Lin; Zhi-Jie Lin; et al. (Science China Life Sciences, 2020)

The NADPH oxidase in Volvariella volvacea and its differential expression in response to mycelial ageing and mechanical injury - Jun-Jie Yan; Zong-Jun Tong; Yuan-Yuan Liu; Zi-Yan Lin; Ying Long; Xing Han; Wei-Nan Xu; Qian-Hui Huang; Yong-Xin Tao; Bao-Gui Xie (Brazilian Journal of Microbiology, 2020)

Aureimonas leprariae sp. nov., Isolated from a Lepraria sp. Lichen - Kun Zhang; Long-Qian Jiang; Li-Song Wang; De-Feng An; Lei Lang; Gui-Ding Li; Xin-Yu Wang; Song-Biao Shi; Qin-Yuan Li; Cheng-Lin Jiang; Yi Jiang (Current Microbiology, 2020)

Rubellimicrobium rubrum sp. nov., a novel bright reddish bacterium isolated from a lichen sample - Long-Qian Jiang; Kun Zhang; Gui-Ding Li; Xin-Yu Wang; Song-Biao Shi; Qin-Yuan Li; De-Feng An; Lei Lang; Li-Song Wang; Cheng-Lin Jiang; Yi Jiang (Antonie van Leeuwenhoek, 2019)

Ottowia flava sp. nov., isolated from fish intestines - Song-Biao Shi; Gui-Ding Li; Li-Fang Yang; Cong Liu; Ming-Guo Jiang; Qin-Yuan Li; Jia-Fa Wu; Kun Zhang; Long-Qian Jiang; Nai-Kun Shen; Cheng-Lin Jiang; Yi Jiang (Antonie van Leeuwenhoek, 2019)

Comparative Transcriptome Analysis Reveals Differentially Expressed Genes and Signaling Pathways Between Male and Female Red-Tail Catfish (Mystus wyckioides) - Jun-Jie Wu; Yu-Lin Zhou; Zhong-Wei Wang; Guang-Hua Li; Fang-Peng Jin; Li-Li Cui; Hai-Tao Gao; Xin-Ping Li; Li Zhou; Jian-Fang Gui (Marine Biotechnology, 2019)

Distinct evolutionary origins of common multi-drug resistance phenotypes in Salmonella typhimurium DT104: a convergent process for adaptation under stress - Le Tang; Song-Ling Zhu; Xin Fang; Yong-Guo Li; Cornelis Poppe; Randal N. Johnston; Gui-Rong Liu; Shu-Lin Liu (Molecular Genetics and Genomics, 2019)

Analysis of the Seismic Effect of Slopes with Different Shapes Under Dynamic Loads - Gui-Lin Wang; Liang Zhang; Zhi-Wen Huang; Bo-Long Liu; Pei-Yong Qiu (Geotechnical and Geological Engineering, 2019)

Early Mesozoic tectonic transition of the eastern South China Block: constraints from Late Triassic Dashuang complex in eastern Zhejiang Province - Xianbing Xu; Qiming Li; Lin Gui; Yuping Su; Xuefen Zhang (International Geology Review, 2019)

Dynamic changes in lakes in the Hoh Xil region before and after the 2011 outburst of Zonag Lake - Wen-hui Liu; Chang-wei Xie; Lin Zhao; Tong-hua Wu; Wu Wang; Yu-xin Zhang; Gui-qian Yang; Xiao-fan Zhu; Guang-yang Yue (Journal of Mountain Science, 2019)

Magnetic mineral diagenesis in sediments of saline lake Lop Nur - Wen Li; Gui-jin Mu; Yong-chong Lin; Hao-ze Song (Journal of Mountain Science, 2019)

Electrode array and data density effects in 3D induced polarization tomography and applications for mineral exploration - Gang Zhang; Qing-Tian Lü; Pin-Rong Lin; Gui-Bin Zhang (Arabian Journal of Geosciences, 2019)

Effects of Long-Term Application of Vinasse on Physicochemical Properties, Heavy Metals Content and Microbial Diversity in Sugarcane Field Soil - Juan Yin; Chao-Bing Deng; Xiao-Fei Wang; Gan-lin Chen; Viktor Gábor Mihucz; Gui-Ping Xu; Qu-Cheng Deng (Sugar Tech, 2019)

A new cyclohexenone from the tin mine tailings-derived fungus Aspergillus flavus YIM DT 10012 - Wei-Xun Chunyu; Jiang-Yuan Zhao; Zhang-Gui Ding; Xiu-Lin Han; Yong-Xia Wang; Jian-Hai Ding; Fei Wang; Ming-Gang Li; Meng-Liang Wen (Natural Product Research, 2019)

The analgesic effect and possible mechanisms by which koumine alters type II collagen-induced arthritis in rats - Gui-Lin Jin; Jian Yang; Wan-Qing Chen; Jie Wang; Hong-Qiang Qiu; Ying Xu; Chang-Xi Yu (Journal of Natural Medicines, 2019)

Evolutionary history of the scorpionfly Dicerapanorpa magna (Mecoptera, Panorpidae) - Gui‐Lin Hu; Yuan Hua; Paul D. N. Hebert; Bao‐Zhen Hua (Zoologica Scripta, 2019)
Climate changes can have fundamental impacts on the distributional patterns of montane species, and range shifts frequently lead to allopatric divergence followed by the establishment of secondary contact zones. Many European and North American organisms have retreated to southern refugia during glacial periods and colonized northward during postglacial periods, but little is known about the evolutionary response of cold‐adapted insects to Pleistocene climate changes in eastern Asia. The scorpionfly Dicerapanorpa magna (Chou), with cold temperate habitat preference and weak dispersal ability, provides a good model system to explore how climate changes have influenced the distribution and divergence of cold‐adapted insects in eastern Asia. This study reconstructed the demographic dynamics and evolutionary history of D. magna with phylogeographic approaches, and predicted the species’ suitable areas under the Last Glacial Maximum (LGM) and current scenarios with the ecological niche modelling analysis. The mitochondrial cytochrome c oxidase subunit I resolved three phylogenetic lineages in D. magna dating back to Pleistocene, corresponding well with the geographically isolated Qinling, Bashan and Minshan Mountains. The ecological niche modelling recovered the suitable habitats for D. magna were the Qinling and Bashan Mountains under LGM and current conditions. The three lineages of D. magna might be in a process of incipient speciation, and likely derived their current distribution from separate glacial origins, followed by vicariance and divergence.

Preference and performance of the two-spotted spider mite Tetranychus urticae (Acari: Tetranychidae) on strawberry cultivars - Ya-Jun Gong; Jin-Cui Chen; Liang Zhu; Li-Jun Cao; Gui-Hua Jin; Ary A. Hoffmann; Chuan-Fei Zhong; Peng Wang; George Lin; Shu-Jun Wei (Experimental and Applied Acarology, 2018)

Summer precipitation anomalies in the low-latitude highlands of China coupled with the subtropical Indian Ocean dipole-like sea surface temperature - Lin Wang; Shu Gui; Jie Cao; Hongming Yan (Climate Dynamics, 2018)

Effect of clay content to the strength of gravel soil in the source region of debris flow - Ning-sheng Chen; Yan-chao Gao; Cheng-lin Yang; Gui-sheng Hu (Journal of Mountain Science, 2018)

Identification and functional analysis of the NLP-encoding genes from the phytopathogenic oomycete Phytophthora capsici - Xiao-Ren Chen; Shen-Xin Huang; Ye Zhang; Gui-Lin Sheng; Yan-Peng Li; Feng Zhu (Molecular Genetics and Genomics, 2018)

Rockburst occurrences and microseismicity in a longwall panel experiencing frequent rockbursts - Zhen-lei Li; Xue-qiu He; Lin-ming Dou; Gui-feng Wang (Geosciences Journal, 2018)

New pyridocarbazole alkaloids from Strychnos nitida - Wei Li; Gui-Hua Tang; Lin Chen; Ya-Qi Tang; You-Kai Xu; Bo Liu; Sheng Yin (Natural Product Research, 2018)

MAVS induces a host cell defense to inhibit CSFV infection - Wang Dong; Huifang Lv; Cheng Li; Yaru Liu; Chengbao Wang; Jihui Lin; Yifan Wang; Gui Qian; Kangkang Guo; Yanming Zhang (Archives of Virology, 2018)

Localization of Maize Critical N Curve and Estimation of NNI by Chlorophyll - Xiao-Gui Liang; Zuo-Lin Zhang; Li-Li Zhou; Si Shen; Zhen Gao; Li Zhang; Shan Lin; Yu-Qiang Pan; Shun-Li Zhou (International Journal of Plant Production, 2018)

Identification and Application of Roof Bed Separation (Water) in Coal Mines - Herong Gui; Manli Lin; Xiaomei Song (Mine Water and the Environment, 2018)

Transcription profiling and identification of infection-related genes in Phytophthora cactorum - Xiao-Ren Chen; Shen-Xin Huang; Ye Zhang; Gui-Lin Sheng; Bo-Yue Zhang; Qi-Yuan Li; Feng Zhu; Jing-You Xu (Molecular Genetics and Genomics, 2018)

Effect of UGT2B7 genotypes on plasma concentration of valproic acid: a meta-analysis - Ping Wang; Xiao-Qian Lin; Wen-Ke Cai; Gui-Li Xu; Meng-Di Zhou; Mei Yang; Gong-Hao He (European Journal of Clinical Pharmacology, 2018)

Joint Interpretation of Geological, Magnetic, AMT, and ERT Data for Mineral Exploration in the Northeast of Inner Mongolia, China - Gang Zhang; Qing-Tian Lü; Gui-Bin Zhang; Ping-Rong Lin; Zheng-Yuan Jia; Kui Suo (Pure and Applied Geophysics, 2018)

Resisting impact mechanical analysis of an anchored roadway supporting structure under P-wave loading and its application in rock burst prevention - Zheng-yi Wang; Lin-ming Dou; Gui-feng Wang; Long-fei Feng; Kai Kang; Jin-zheng Bai; Sheng-chuan Wang (Arabian Journal of Geosciences, 2018)

The Distal Gut Bacterial Community of Some Primates and Carnivora - Xiu Chen; Qin-Yuan Li; Gui-Ding Li; Fang-Ji Xu; Li Han; Yi Jiang; Xue-Shi Huang; Cheng-Lin Jiang (Current Microbiology, 2018)

Water allocation under the constraint of total water-use quota: a case from Dongjiang River Basin, South China - Yanhu He; Xiaohong Chen; Zhuping Sheng; Kairong Lin; Faliang Gui (Hydrological Sciences Journal, 2018)

Effects of prenatal caffeine exposure on glucose homeostasis of adult offspring rats - Hao Kou; Gui-hua Wang; Lin-guo Pei; Li Zhang; Chai Shi; Yu Guo; Dong-fang Wu; Hui Wang (The Science of Nature, 2017)

Two new diketopiperazines from the tin mine tailings-derived fungus Schizophyllum commune YIM DT 10058 - Wei-Xun Chunyu; Zhang-Gui Ding; Jiang-Yuan Zhao; Yong-Xia Wang; Xiu-Lin Han; Ming-Gang Li; Meng-Liang Wen (Natural Product Research, 2017)

Water-inrush mechanism research mining above karst confined aquifer and applications in North China coalmines - Herong Gui; Xiaomei Song; Manli Lin (Arabian Journal of Geosciences, 2017)

Enterovirga rhinocerotis gen. nov., sp. nov., isolated from Rhinoceros unicornis faeces - Xiu Chen; Qin-Yuan Li; Gui-Ding Li; Hui Lei; Yi Jiang; Li Han; Xue-Shi Huang; Cheng-Lin Jiang (Antonie van Leeuwenhoek, 2017)

A novel thymidine phosphorylase mutation in a Chinese MNGIE patient - Hui-Fang Wang; Juan Wang; Yan-Ling Wang; Jian-Jian Fan; Gui-Lin Mo; Feng-Yin Gong; Zhi-Ming Chai; Jin Zhang; Hua-Xing Meng; Chang-Xin Li; Jun-Hong Guo; Chuan-Qiang Pu (Acta Neurologica Belgica, 2017)

Quantifying the changing properties of climate extremes in Guangdong Province using individual and integrated climate indices - Yanhu He; Kairong Lin; Guoping Tang; Xiaohong Chen; Shenglian Guo; Faliang Gui (International Journal of Climatology, 2017)
The temporal and spatial trends of four climate extreme indices for Guangdong Province of China were calculated based on observed daily precipitation, daily maximum, and daily minimum temperatures at 24 weather stations as well as the frequency of typhoon events during the period of 1957–2013. An integrated extreme climatic index ( IECI ) was derived from four individual climate extreme indices (high temperature days ( H td ), low temperature days ( L td ), intensive precipitation days ( I pd ) and number of typhoon events ( TT )), considering their weights using an information theory model. A simple linear regression model was utilized to analyze the spatiotemporal trends of the climate extremes. The correlation analysis between the above extreme climatic indices and the socioeconomic losses [affected area of crops ( AAC ), direct losses of the economy ( DLE ), and affected population ( AP )] was calculated. The results indicate that H td increased while L td decreased significantly at the 5% significance level. By contrast, there were no significant long‐term changes in I pd and TT . The rate of change of IECI was 0.006 per decade and no long‐term trend was detected in IECI . Spatially, a positive trend was observed in the Yuexi River Basin ( YXRB ) for I pd , while a negative trend was found in the East River Basin ( ERB ). L td followed an opposite spatial pattern to that of H td . Extreme temperature days occurred more frequently in the Pearl River Delta ( PRD ) than in other parts of Guangdong Province. Regions with positive IECI rates of change were mostly in the YXRB , the coastal area of the Yuedong River Basin ( YDRB ) and the northern and southern part of the ERB . The correlation coefficients between IECI and AAC , DLE , and AP are 0.375, 0.424 and 0.603, respectively. In general, IECI correlated more strongly with the loss indices caused by extreme climatic events than did the four individual extreme climatic indices.

Two new compounds from Trollius chinensis Bunge - Ya Jie-Shi; Lin Wei-Sang; Rui Yan; Qiang Zhao; Yang Zhang; Gui Yun-Zhao; Yun Cong-Li; Xue Chen; Chong Yu-Zhang; Hua Qiao; Guo Gang-Zhang (Journal of Natural Medicines, 2017)

Pollution characteristics, source apportionment, and health risk of heavy metals in street dust of Suzhou, China - Manli Lin; Herong Gui; Yao Wang; Weihua Peng (Environmental Science and Pollution Research, 2017)

Limit analysis method for active earth pressure on laggings between stabilizing piles - Ming-min Wang; Shu-guang Wu; Gui-lin Wang (Journal of Mountain Science, 2017)

Strength, Deformability and X-ray Micro-CT Observations of Deeply Buried Marble Under Different Confining Pressures - Sheng-Qi Yang; Yang Ju; Feng Gao; Yi-Lin Gui (Rock Mechanics and Rock Engineering, 2016)

Types of water hazards in China coalmines and regional characteristics - Herong Gui; Manli Lin (Natural Hazards, 2016)

Tripchlorolide Attenuates β-amyloid Generation via Suppressing PPARγ-Regulated BACE1 Activity in N2a/APP695 Cells - Nan Lin; Li-min Chen; Xiao-dong Pan; Yuan-gui Zhu; Jing Zhang; Yan-qing Shi; Xiao-chun Chen (Molecular Neurobiology, 2016)

Outlining a stepwise, multi-parameter debris flow monitoring and warning system: an example of application in Aizi Valley, China - Ning-sheng Chen; Javed Iqbal Tanoli; Gui-sheng Hu; Feng-niang Wang; Cheng-lin Yang; Hai-tao Ding; Na He; Tao Wang (Journal of Mountain Science, 2016)

Microbacterium gilvum sp. nov., isolated from civet faeces - Xiu Chen; Qin-Yuan Li; Gui-Ding Li; Fang-Ji Xu; Yi Jiang; Li Han; Cheng-Lin Jiang; Xue-Shi Huang (Antonie van Leeuwenhoek, 2016)

Historical biogeography of the short‐faced scorpionflies (Insecta: Mecoptera: Panorpodidae) - Gui‐Lin Hu; Bao‐Zhen Hua (Journal of Biogeography, 2016)
Aim Panorpodidae is a species‐poor family of Mecoptera, containing only 13 species in its two genera, Panorpodes and Brachypanorpa . They are found disjunctly in eastern Asia and North America, and this distribution has been deeply affected by the region's complex geological and climatic history. We calculate a time‐calibrated molecular phylogeny and use it to reconstruct the historical biogeography of the Panorpodidae, in order to explore the family's phylogenetic origin and the biogeographical process that resulted in the present disjunct distribution. Location Eastern Asia and North America. Methods Sequence data from mitochondrial ( COI and COII ) and nuclear DNA ( 28S and EF ‐1 α) were assembled from eight ingroup species. A phylogeny was reconstructed using maximum‐likelihood analysis and Bayesian inference, and divergence times were estimated using fossil‐calibrated Bayesian analysis. Ancestral areas were reconstructed with rasp 3.02, implementing dispersal–vicariance analysis, dispersal–extinction–cladogenesis and Bayesian binary MCMC . Results The initial diversification of Panorpodidae occurred during the Ypresian ( c. 53.9 Ma). A wide ancestral distribution in eastern Asia and western North America was inferred from the biogeographical analyses. The original range of Panorpodes across eastern Asia and western North America was fragmented by intercontinental vicariance. The genus Brachypanorpa was initially restricted to western North America and subsequently dispersed into eastern regions of North America. Main conclusions Two alternative biogeographical patterns were recovered. Either Panorpodidae was restricted to western North America in the Eocene and subsequently dispersed into eastern Asia or – more reasonably – it was widely distributed in western North America, eastern Asia and Europe during the Eocene. Our biogeographical reconstructions corroborate the significant role of vicariance in shaping the current eastern Asian and North American disjunction in Panorpodes . The geographical separation of western and eastern North American Brachypanorpa species is likely to have resulted from the uplift of the Rocky Mountains and the emergence of grassland biomes in central North America.

Evolution of Stress Concentration and Energy Release Before Rock Bursts: Two Case Studies from Xingan Coal mine, Hegang, China - Gui-feng Wang; Si-yuan Gong; Zhen-lei Li; Lin-ming Dou; Wu Cai; Yong Mao (Rock Mechanics and Rock Engineering, 2016)

SSR-based genetic mapping and QTL analysis for timing of spring bud flush, young shoot color, and mature leaf size in tea plant (Camellia sinensis) - Li-Qiang Tan; Li-Yuan Wang; Li-Yi Xu; Li-Yun Wu; Min Peng; Cheng-Cai Zhang; Kang Wei; Pei-Xian Bai; Hai-Lin Li; Hao Cheng; Gui-Nian Qi (Tree Genetics & Genomes, 2016)

Efficacy of a Fructus mume Extract Combination with Stable Chlorine in Preventing Bacterial Contamination in Frozen Mackerel ( Scomber japonicus ) Fillets - Bin Zhang; Hui-min Lin; Yan Tang; Shang-gui Deng (Journal of Aquatic Food Product Technology, 2016)

Comparison of vitrified outcomes between human early blastocysts and expanded blastocysts - Wen-yan Song; Xue-gai Wang; Hai-xia Jin; Gui-dong Yao; Xiang-yang Zhang; Sen-lin Shi; Hong-yi Yang; Zhao-feng Peng; Ying-pu Sun (In Vitro Cellular & Developmental Biology - Animal, 2016)

Hydrochemical characteristics and quality assessment of deep groundwater from the coal-bearing aquifer of the Linhuan coal-mining district, Northern Anhui Province, China - Man-li Lin; Wei-hua Peng; He-rong Gui (Environmental Monitoring and Assessment, 2016)

Heavy metals in deep groundwater within coal mining area, northern Anhui province, China: concentration, relationship, and source apportionment - Manli Lin; Weihua Peng; Herong Gui (Arabian Journal of Geosciences, 2016)

Mechanical Analysis of Static Stress Within Fault-Pillars Based on a Voussoir Beam Structure - Zhen-lei Li; Lin-ming Dou; Wu Cai; Gui-feng Wang; Yan-lu Ding; Yong Kong (Rock Mechanics and Rock Engineering, 2016)

Roadway Stagger Layout for Effective Control of Gob-Side Rock Bursts in the Longwall Mining of a Thick Coal Seam - Zhen-lei Li; Lin-ming Dou; Wu Cai; Gui-feng Wang; Yan-lu Ding; Yong Kong (Rock Mechanics and Rock Engineering, 2016)

Enteractinococcus lamae sp. nov. and Enteractinococcus viverrae sp. nov., isolated from animal faeces - Xiu Chen; Gui-Ding Li; Qin-Yuan Li; Cai-Juan Hu; Shu-Mei Qiu; Yi Jiang; Cheng-Lin Jiang; Li Han; Xue-Shi Huang (Antonie van Leeuwenhoek, 2015)

Sphingobacterium rhinocerotis sp. nov., isolated from the faeces of Rhinoceros unicornis - Gui-Ding Li; Xiu Chen; Qin-Yuan Li; Fang-Ji Xu; Shu-Mei Qiu; Yi Jiang; Cheng-Lin Jiang (Antonie van Leeuwenhoek, 2015)

New sesquiterpenoid derivatives from Solanum septemlobum with cytotoxicities - Lei Zhang; Hai-Qing Lin; Gui-Sheng Li; Xi-Dian Yue; Sheng-Jun Dai (Natural Product Research, 2015)

Microcalorimetry studies of the antimicrobial actions of Aconitum alkaloids - Yan-bin Shi; Lian Liu; Wei Shao; Ting Wei; Gui-mei Lin (Journal of Zhejiang University-SCIENCE B, 2015)

Phylogenetic and recombination analysis of rice black-streaked dwarf virus segment 9 in China - Yu Zhou; Jian-Feng Weng; Yan-Ping Chen; Chang-Lin Liu; Xiao-Hua Han; Zhuan-Fang Hao; Ming-Shun Li; Hong-Jun Yong; De-Gui Zhang; Shi-Huang Zhang; Xin-Hai Li (Archives of Virology, 2015)

Conjugated linoleic acid alters growth performance, tissue lipid deposition, and fatty acid composition of darkbarbel catfish (Pelteobagrus vachelli) - Gui-Fang Dong; Wen-Zuo Liu; Lin-Zhou Wu; Deng-hang Yu; Feng Huang; Peng-Cheng Li; Yan-ou Yang (Fish Physiology and Biochemistry, 2015)

Changes of Serum Osteocalcin, Calcium, and Potassium in a Rat Model of Type 2 Diabetes - Lin Xiao; Xian Mo Wang; Tao Yang; Ying Xiong; Zhong Gui Zhang; Jun Ding; Chen Xu; Chang Yuan Xiong (Cell Biochemistry and Biophysics, 2015)

Gray and white matter structures in the midcingulate cortex region contribute to body mass index in Chinese young adults - Qinghua He; Chuansheng Chen; Qi Dong; Gui Xue; Chunhui Chen; Zhong-Lin Lu; Antoine Bechara (Brain Structure and Function, 2015)

Effects of boron toxicity on root and leaf anatomy in two Citrus species differing in boron tolerance - Jing-Hao Huang; Zi-Jian Cai; Shou-Xing Wen; Peng Guo; Xin Ye; Gui-Zhu Lin; Li-Song Chen (Trees, 2014)

Coordinated regulation of autophagy and apoptosis determines endothelial cell fate during Dengue virus type 2 infection - Junqi Huang; Ying Li; Yiming Qi; Yingke Zhang; Lin Zhang; Zilian Wang; Xuzhi Zhang; Lian Gui (Molecular and Cellular Biochemistry, 2014)

Isolation and characterization of polymorphic microsatellites in the perennial herb Euphorbia kansui using paired-end Illumina shotgun sequencing - Xiao-Hao Yan; Min-Feng Fang; Zeng-Qiang Qian; Zhan-Lin Liu; Ma-Li Wang; Cai-Ping Tian; Meng-Han Du; Yin-Jun Li; Zhong-Hu Li; Gui-Fang Zhao (Conservation Genetics Resources, 2014)

Pore structure effect on reservoir electrical properties and well logging evaluation - Huan-Lin Bian; Ju Guan; Zhi-Qiang Mao; Xiao-Dong Ju; Gui-Qing Han (Applied Geophysics, 2014)

Fosinopril improves the electrophysiological characteristics of left ventricular hypertrophic myocardium in spontaneously hypertensive rats - Zhi-Bin Huang; Chun-Yu Deng; Mao-Huan Lin; Gui-Yi Yuan; Wei Wu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2014)

A study of shear strength properties of municipal solid waste in Chongqing landfill, China - Yan Ru Zhao; Qiang Xie; Gui Lin Wang; Yong Jian Zhang; Yong Xing Zhang; Wenjun Su (Environmental Science and Pollution Research, 2014)

The Protective Effect of a Metallic Selenopeptide with Superoxide Dismutase and Glutathione Peroxidase Activities Against Alcohol Induced Injury in Hepatic L02 Cells - Wang Cheng; Shen Na; Yan Gang-lin; Sui Chun-hong; Zhuang Jian-jian; Lü Shao-wu; Luo Gui-min; Mu Ying (International Journal of Peptide Research and Therapeutics, 2014)

Detection and Characterization of Avastrovirus Associated with Diarrhea Isolated from Minks in China - Na Sun; Yong Yang; Gui-Sheng Wang; Xi-Qun Shao; Shu-Qin Zhang; Feng-Xue Wang; Bin Tan; Fu-Lin Tian; Shi-Peng Cheng; Yong-Jun Wen (Food and Environmental Virology, 2014)

Molecular evidence reveals the distinctiveness of Indo-Pacific finless porpoises (Neophocaena phocaenoides) in the Pearl River Estuary and insights into genus Neophocaena’s origin - Kuntong Jia; Wenzhi Lin; Duan Gui; Leszek Karczmarski; Yuping Wu (Marine Biology, 2014)

Complete genome sequence analysis identifies a new genotype of brassica yellows virus that infects cabbage and radish in China - Xiao-Yan Zhang; Hai-Ying Xiang; Cui-Ji Zhou; Da-Wei Li; Jia-Lin Yu; Cheng-Gui Han (Archives of Virology, 2014)

Neuronal and Astroglial TGFβ-Smad3 Signaling Pathways Differentially Regulate Dendrite Growth and Synaptogenesis - Chuan-Yong Yu; Wei Gui; Hui-Yan He; Xiao-Shan Wang; Jian Zuo; Lin Huang; Nong Zhou; Kai Wang; Yu Wang (NeuroMolecular Medicine, 2014)

Pulmonary Toxicity in Mice Following Exposure to Cerium Chloride - Jie Hong; Xiaohong Yu; Xiaoyu Pan; Xiaoyang Zhao; Lei Sheng; Xuezi Sang; Anan Lin; Chi Zhang; Yue Zhao; Suxin Gui; Qingqing Sun; Ling Wang; et al. (Biological Trace Element Research, 2014)

Effect of fosinopril on the transient outward potassium current of hypertrophied left ventricular myocardium in the spontaneously hypertensive rat - Huang Zhi-bin; Fang Chang; Lin Mao-huan; Yuan Gui-yi; Zhou Shu-xian; Wu Wei (Naunyn-Schmiedeberg's Archives of Pharmacology, 2014)

Erratum to: Bacillus bingmayongensis sp. nov., isolated from the pit soil of Emperor Qin’s Terra-cotta warriors in China - Bo Liu; Guo-Hong Liu; Gui-Ping Hu; Cetin Sengonca; Nai-Quan Lin; Jian-Yang Tang; Wei-Qi Tang; Ying-Zhi Lin (Antonie van Leeuwenhoek, 2014)

Bacillus bingmayongensis sp. nov., isolated from the pit soil of Emperor Qin’s Terra-cotta warriors in China - Bo Liu; Guo-Hong Liu; Gui-Ping Hu; Sengonca Cetin; Nai-Quan Lin; Jian-Yang Tang; Wei-Qi Tang; Ying-Zhi Lin (Antonie van Leeuwenhoek, 2014)

A new benzopyran derivative from Pseuduvaria indochinensis Merr. - Cai-Gui Zhao; Ming-Jun Yao; Jin-Wei Yang; Ya-Lin Chai; Xiao-Dong Sun; Cheng-Shan Yuan (Natural Product Research, 2014)

Litter decomposition of a pine plantation is affected by species evenness and soil nitrogen availability - Gui-Gang Lin; Rong Mao; Lei Zhao; De-Hui Zeng (Plant and Soil, 2013)

Genomic comparison of Salmonella typhimurium DT104 with non-DT104 strains - Er-Ying Zhao; Hong-Xia Bao; Le Tang; Qing-Hua Zou; Wei-Qiao Liu; Da-Ling Zhu; Jessica Chin; Ying-Ying Dong; Yong-Guo Li; Feng-Lin Cao; Cornelis Poppe; Kenneth E. Sanderson; et al. (Molecular Genetics and Genomics, 2013)

Abnormal baseline brain activity in patients with HBV-related cirrhosis without overt hepatic encephalopathy revealed by resting-state functional MRI - Xiao-Fei Lv; Min Ye; Lu-Jun Han; Xue-Lin Zhang; Pei-Qiang Cai; Gui-Hua Jiang; Ying-Wei Qiu; Shi-Jun Qiu; Yao-Pan Wu; Kai Liu; Zhen-Yin Liu; Pei-Hong Wu; et al. (Metabolic Brain Disease, 2013)

Isolation and characterization of polymorphic microsatellite loci in Ping’s juniper Juniperus pingii - Zhong-Hu Li; Zhan-Lin Liu; Yu-Jin Wang; Min-Feng Fang; Ma-Li Wang; Zhi-Xuan Li; Gui-Fang Zhao (Conservation Genetics Resources, 2013)

Cerebral blood flow and metabolic changes in hippocampal regions of a modified rat model with chronic cerebral hypoperfusion - Hai Jian; Wu Yi-Fang; Lin Qi; Huang Xiao-Song; Zhang Gui-Yun (Acta Neurologica Belgica, 2013)

Analysis of artificial corner reflector’s radar cross section: a physical optics perspective - Xin-Jian Shan; Jing-Yuan Yin; Dan-Lin Yu; Cheng-Fan Li; Jun-Juan Zhao; Gui-Fang Zhang (Arabian Journal of Geosciences, 2013)

Screening Chinese soybean genotypes for Agrobacterium-mediated genetic transformation suitability - Zhang-yue Song; Jing-luan Tian; Wei-zhe Fu; Lin Li; Ling-hong Lu; Lian Zhou; Zhi-hui Shan; Gui-xiang Tang; Hui-xia Shou (Journal of Zhejiang University-SCIENCE B, 2013)

Pseudomonas aeruginosa isolates of distinct sub-genotypes exhibit similar potential of antimicrobial resistance by drugs exposure - Zhen-Hong Liu; Yan Xu; Li-Bo Duo; Yu Liu; Zhao-Zhen Xu; Jane L. Burns; Gui-Rong Liu; Bao-Feng Yang; Shu-Lin Liu (Antonie van Leeuwenhoek, 2013)

Spatial patterns and climate drivers of carbon fluxes in terrestrial ecosystems of China - Gui‐Rui Yu; Xian‐Jin Zhu; Yu‐Ling Fu; Hong‐Lin He; Qiu‐Feng Wang; Xue‐Fa Wen; Xuan‐Ran Li; Lei‐Ming Zhang; Li Zhang; Wen Su; Sheng‐Gong Li; Xiao‐Min Sun; et al. (Global Change Biology, 2013)
Understanding the dynamics and underlying mechanism of carbon exchange between terrestrial ecosystems and the atmosphere is one of the key issues in global change research. In this study, we quantified the carbon fluxes in different terrestrial ecosystems in China, and analyzed their spatial variation and environmental drivers based on the long‐term observation data of China FLUX sites and the published data from other flux sites in China. The results indicate that gross ecosystem productivity ( GEP ), ecosystem respiration ( ER ), and net ecosystem productivity ( NEP ) of terrestrial ecosystems in China showed a significantly latitudinal pattern, declining linearly with the increase of latitude. However, GEP , ER , and NEP did not present a clear longitudinal pattern. The carbon sink functional areas of terrestrial ecosystems in China were mainly located in the subtropical and temperate forests, coastal wetlands in eastern China, the temperate meadow steppe in the northeast China, and the alpine meadow in eastern edge of Qinghai‐Tibetan Plateau. The forest ecosystems had stronger carbon sink than grassland ecosystems. The spatial patterns of GEP and ER in China were mainly determined by mean annual precipitation ( MAP ) and mean annual temperature ( MAT ), whereas the spatial variation in NEP was largely explained by MAT . The combined effects of MAT and MAP explained 79%, 62%, and 66% of the spatial variations in GEP , ER , and NEP , respectively. The GEP , ER , and NEP in different ecosystems in China exhibited ‘positive coupling correlation’ in their spatial patterns. Both ER and NEP were significantly correlated with GEP , with 68% of the per‐unit GEP contributed to ER and 29% to NEP . MAT and MAP affected the spatial patterns of ER and NEP mainly by their direct effects on the spatial pattern of GEP .

Two new triterpenoid saponins from Caragana microphylla seeds - Cheng-Jian Zheng; Gui-Lin Jin; Jing-Ping Zou; Yi-Ping Jiang; Pei-Xin Sun; Lu-Ping Qin (Journal of Natural Medicines, 2013)

Effects of Sub-soil Drip Fertigation on Sugarcane in Field Conditions - Gui-Fen Chen; Qi-Zhan Tang; Yang-Rui Li; Yu-Yi Huang; Bin Liu; Lin Xu; Hai-Rong Huang (Sugar Tech, 2012)

Low-intensity pulsed ultrasound therapy: a potential strategy to stimulate tendon-bone junction healing - Zhi-min Ying; Tiao Lin; Shi-gui Yan (Journal of Zhejiang University-SCIENCE B, 2012)

Docetaxel-loaded liposomes: preparation, pH sensitivity, Pharmacokinetics, and tissue distribution - Hong Zhang; Rui-ying Li; Xia Lu; Zhen-zhen Mou; Gui-mei Lin (Journal of Zhejiang University-SCIENCE B, 2012)

Urban Phosphorus Metabolism through Food Consumption - Gui‐Lin Li; Xuemei Bai; Shen Yu; Hua Zhang; Yong‐Guan Zhu (Journal of Industrial Ecology, 2012)
Summary Urbanization has significant impacts on local, regional, and global biogeochemical cycles, including through nutrient enrichment by food consumption, and especially in rapidly urbanizing countries. This article presents a time‐series estimation of phosphorus (P) metabolism through food consumption in Chinese cities and examines its relationship to income level during the period 1985–2006. Our results show that approximately 39% of the total dietary P inflow is exported through direct sewage discharge without treatment, 35% is exported via the output of solid human excreta, 7% is exported through sewage sludge landfill, and 19% is left within urban areas. The total inflow of dietary P to urban systems increases with per capita disposable income level. Furthermore, the ratio of dietary P remaining in urban systems to total dietary P inflow, the dietary P remaining in urban systems per capita, and the dietary P remaining per unit urban built‐up area respond in an inverted U shape to increases in per capita disposable income; the per capita outflow of dietary P shows a U‐shaped response. These relationships may indicate that the impact of urban dietary P on urban environmental systems follows the traditional environmental Kuznets curve, while the environmental impact of urban dietary P on surrounding nonurban ecosystems initially decreases but then increases with the rising income of urban residents.

Analysis of Isocitrate Dehydrogenase 1 Mutation in 97 Patients with Glioma - You-Xin Zhou; Jun-Xiang Wang; Ming Feng; Chun-Ming Sun; Ting Sun; Gui-Lin Chen; Zi-Wei Du (Journal of Molecular Neuroscience, 2012)

Nucleotide sequence of a chickpea chlorotic stunt virus relative that infects pea and faba bean in China - Cui-Ji Zhou; Hai-Ying Xiang; Tao Zhuo; Da-Wei Li; Jia-Lin Yu; Cheng-Gui Han (Archives of Virology, 2012)

Drug-related cues exacerbate decision making and increase craving in heroin addicts at different abstinence times - Gui-Bin Wang; Xiao-Li Zhang; Li-Yan Zhao; Li-Li Sun; Ping Wu; Lin Lu; Jie Shi (Psychopharmacology, 2012)

Proteomic Analysis of Osmotic Stress-Responsive Proteins in Sugarcane Leaves - Gui Zhou; Li-Tao Yang; Yang-Rui Li; Cheng-Lin Zou; Li-Ping Huang; Li-Hang Qiu; Xing Huang; Manoj Kumar Srivastava (Plant Molecular Biology Reporter, 2012)

Complete genomic sequence analysis reveals a novel fabavirus infecting cucurbits in China - Shu-Wei Dong; Hai-Ying Xiang; Qiao-Xia Shang; Da-Wei Li; Jia-Lin Yu; Cheng-Gui Han (Archives of Virology, 2012)

Dew water isotopic ratios and their relationships to ecosystem water pools and fluxes in a cropland and a grassland in China - Xue-Fa Wen; Xuhui Lee; Xiao-Min Sun; Jian-Lin Wang; Zhong-Min Hu; Sheng-Gong Li; Gui-Rui Yu (Oecologia, 2012)

A Novel Mutation in CACNA1S Gene Associated with Hypokalemic Periodic Paralysis Which has a Gender Difference in the Penetrance - Fei-Feng Li; Qian-Qian Li; Zhen-Xuan Tan; Si-Yao Zhang; Ji Liu; Er-ying Zhao; Gui-Chun Yu; Jin Zhou; Li-Ming Zhang; Shu-Lin Liu (Journal of Molecular Neuroscience, 2012)

Donor-Acceptor Compound Based on Rhodanineacetic Acid-Pyrene Derivative: Red-Light Emitting Fluorescent Organic Nanoparticles - Bo Zhang; Wei Diao; Chun Bi; Jian Sun; Guoxia Han; Yi Shi; Li Sheng; Gui Yin; Lin Pu (Journal of Fluorescence, 2012)

First Isolation of Candida dubliniensis from Oral Cavities of Dermatological Patients in Nanjing, China - Yi P. Ge; Guo X. He; Tong Lin; Gui X. Lu; Yong N. Shen; Wei D. Liu (Mycopathologia, 2011)

Molecular characterization of two genotypes of a new polerovirus infecting brassicas in China - Hai-Ying Xiang; Shu-Wei Dong; Qiao-Xia Shang; Cui-Ji Zhou; Da-Wei Li; Jia-Lin Yu; Cheng-Gui Han (Archives of Virology, 2011)

Antioxidant Responses and Bioaccumulation in Green-lipped Mussels (Perna Viridis) Under Acute Tributyltin Chloride Exposure - Hai-Gang Chen; Xiao-Ping Jia; Wen-Gui Cai; Qin Lin; Sheng-Wei Ma (Bulletin of Environmental Contamination and Toxicology, 2011)

Microcalorimetry studies on the antibacterial effect of crude monkshood polysaccharide - Gui-mei Lin; Lian Liu; Wei Shao (Journal of Zhejiang University-SCIENCE B, 2011)

Aucubin modulates Bcl-2 family proteins expression and inhibits caspases cascade in H2O2-induced PC12 cells - Hong Yu Xue; Dong Yan Niu; Gui Zhen Gao; Qiu Ye Lin; Li Ji Jin; Yong Ping Xu (Molecular Biology Reports, 2011)

Factors altering the membrane fluidity of spinach thylakoid as determined by fluorescence polarization - Zhi Fang Lin; Nan Liu; Gui Zhu Lin; Chang Lian Peng (Acta Physiologiae Plantarum, 2011)

Trichodermanin A, a novel diterpenoid from endophytic fungus culture - Pei-Xin Sun; Cheng-Jian Zheng; Wen-Chao Li; Gui-Lin Jin; Fang Huang; Lu-Ping Qin (Journal of Natural Medicines, 2011)

Enhancement of salt tolerance in alfalfa transformed with the gene encoding for betaine aldehyde dehydrogenase - Zi-Hui Liu; Hong-Mei Zhang; Guo-Liang Li; Xiu-Lin Guo; Shou-Yi Chen; Gui-Bo Liu; Yan-Min Zhang (Euphytica, 2011)

Analysis of the Composition and Characteristics of Culturable Endophytic Bacteria Within Subnival Plants of the Tianshan Mountains, Northwestern China - Hong Mei Sheng; Hong Shan Gao; Lin Gui Xue; Shuo Ding; Chun Li Song; Hu Yuan Feng; Li Zhe An (Current Microbiology, 2011)

A novel strain of Beet western yellows virus infecting sugar beet with two distinct genotypes differing in the 5′-terminal half of genome - Cui-Ji Zhou; Hai-Ying Xiang; Tao Zhuo; Da-Wei Li; Jia-Lin Yu; Cheng-Gui Han (Virus Genes, 2011)

Arbuscular mycorrhizal fungal community structure and diversity in response to long-term fertilization: a field case from China - Fa Yuan Wang; Jun Li Hu; Xian Gui Lin; Sheng Wu Qin; Jun Hua Wang (World Journal of Microbiology and Biotechnology, 2011)

Somatic embryogenesis and organogenesis in Dendrocalamus hamiltonii - Ning Zhang; Wei Fang; Yan Shi; Qianqian Liu; Haiyun Yang; Renyi Gui; Xinchun Lin (Plant Cell, Tissue and Organ Culture (PCTOC), 2010)

Nicotine dependence and serum BDNF levels in male patients with schizophrenia - Xiang Yang Zhang; Mei Hong Xiu; Da Chun Chen; Fu De Yang; Gui Ying Wu; Lin Lu; Therese A. Kosten; Thomas R. Kosten (Psychopharmacology, 2010)

Ecotoxicity assessment of aged petroleum sludge using a suite of effects-based end points in earthworm Eisenia fetida - Shi-Jie Wang; Zeng-Guang Yan; Guan-Lin Guo; Gui-Lan Lu; Qun-Hui Wang; Fa-Sheng Li (Environmental Monitoring and Assessment, 2010)

Occurrence and distribution of polycyclic aromatic carbons in sludges from wastewater treatment plants in Guangdong, China - Xiangying Zeng; Zheng Lin; Hongyan Gui; Wenlan Shao; Guoying Sheng; Jiamo Fu; Zhiqiang Yu (Environmental Monitoring and Assessment, 2010)

Altered Expression of the Small Guanosine Triphosphatase RhoA in Human Temporal Lobe Epilepsy - Jie Yuan; Lin-yuan Wang; Jin-mei Li; Ning-jia Cao; Liang Wang; Gui-bo Feng; Tao Xue; Yang Lu; Xue-feng Wang (Journal of Molecular Neuroscience, 2010)

Molecular characterization of two Chinese isolates of Beet western yellows virus infecting sugar beet - Hai-Ying Xiang; Shu-Wei Dong; Hui-Zhong Zhang; Wei-Lin Wang; Min-Quan Li; Cheng-Gui Han; Da-Wei Li; Jia-Lin Yu (Virus Genes, 2010)

Excretion of PFOA and PFOS in Male Rats During a Subchronic Exposure - Lin Cui; Chun-yang Liao; Qun-fang Zhou; Tong-mei Xia; Zhao-jun Yun; Gui-bin Jiang (Archives of Environmental Contamination and Toxicology, 2010)

Light acclimation and HSO3 − damage on photosynthetic apparatus of three subtropical forest species - Nan Liu; Zhi-Fang Lin; Lan-Lan Guan; Gui-Zhu Lin; Chang-Lian Peng (Ecotoxicology, 2009)

Isolation and characterization of polymorphic microsatellite loci from fat greenling (Hexagrammos otakii) - Song-Lin Chen; Gui-Dong Miao; Chang-Wei Shao; Yong-Sheng Tian; Xiaolin Liao (Conservation Genetics, 2009)

Isolation and characterization of 12 microsatellite loci from cutlassfish (Trichiurus haumela) - Jin-Zhen Bi; Chang-Wei Shao; Gui-Dong Miao; Hong-Yu Ma; Song-Lin Chen (Conservation Genetics, 2009)

Isolation and characterization of polymorphic microsatellite loci from a repeat-enriched genomic library of stone flounder (Kareius bicoloratus) and cross-species amplification - Yong-Sheng Tian; Gui-Dong Miao; Chang-Wei Shao; Xiao-Lin Liao; Song-Lin Chen (Conservation Genetics, 2009)

In Situ Localisation of Superoxide Generated in Leaves of Alocasia macrorrhiza (L.) Shott under Various Stresses - Zhi-Fang Lin; Nan Liu; Gui-Zhu Lin; Chang-Lian Peng (Journal of Plant Biology, 2009)

A ThCAP gene from Tamarix hispida confers cold tolerance in transgenic Populus (P. davidiana × P. bolleana) - Xiao-Hong Guo; Jing Jiang; Shi-Jie Lin; Bai-Chen Wang; Yu-Cheng Wang; Gui-Feng Liu; Chuan-Ping Yang (Biotechnology Letters, 2009)

Effect of CO2 enrichment on the glucosinolate contents under different nitrogen levels in bolting stem of Chinese kale (Brassica alboglabra L.) - Gui-xiao La; Ping Fang; Yi-bo Teng; Ya-juan Li; Xian-yong Lin (Journal of Zhejiang University-SCIENCE B, 2009)

Development of polymorphic microsatellite markers from barfin flounder (Verasper moseri) and their cross-species amplification - Gui-Dong Miao; Chang-Wei Shao; Xiao-Lin Liao; Hong-Yu Ma; Yong-Sheng Tian; Song-Lin Chen (Conservation Genetics, 2009)

Superoxide dismutase and cytokines in chronic patients with schizophrenia: association with psychopathology and response to antipsychotics - Xiang Yang Zhang; Dong Feng Zhou; Ling Yan Qi; Song Chen; Lian Yuan Cao; Da Chun Chen; Mei Hong Xiu; Fan Wang; Gui Ying Wu; Lin Lu; Therese A. Kosten; Thomas R. Kosten (Psychopharmacology, 2009)

Molecular cloning and recombinant expression of a gene encoding a fungal immunomodulatory protein from Ganoderma lucidum in Pichia pastoris - Jing-Wei Lin; Li-Xia Hao; Gui-Xue Xu; Fei Sun; Feng Gao; Ren Zhang; Li-Xia Liu (World Journal of Microbiology and Biotechnology, 2009)

Studies on the Toxicological Effects of PFOA and PFOS on Rats Using Histological Observation and Chemical Analysis - Lin Cui; Qun-fang Zhou; Chun-yang Liao; Jian-jie Fu; Gui-bin Jiang (Archives of Environmental Contamination and Toxicology, 2009)

Lower serum cytokine levels in smokers than nonsmokers with chronic schizophrenia on long-term treatment with antipsychotics - Xiang Yang Zhang; Lian Yuan Cao; Cai Song; Gui Ying Wu; Da Chun Chen; Ling Yan Qi; Fan Wang; Mei Hong Xiu; Song Chen; Yingyang Zhang; Lin Lu; Therese A. Kosten; et al. (Psychopharmacology, 2008)

Cloning and expression study of a putative carotene biosynthesis related (cbr) gene from the halotolerant green alga Dunaliella salina - Chen Chen; Lin Han Bai; Dai Rong Qiao; Hui Xu; Gui Ling Dong; Kun Ruan; Fei Huang; Yi Cao (Molecular Biology Reports, 2008)

Vertical distribution, biomass, production and turnover of fine roots along a topographical gradient in a sandy shrubland - Gang Huang; Xue-yong Zhao; Yan-gui Su; Ha-lin Zhao; Tong-hui Zhang (Plant and Soil, 2008)

Complete sequence analysis reveals two distinct poleroviruses infecting cucurbits in China - Hai-ying Xiang; Qiao-xia Shang; Cheng-gui Han; Da-wei Li; Jia-lin Yu (Archives of Virology, 2008)

Stress-Induced Alteration of Chlorophyll Fluorescence Polarization and Spectrum in Leaves of Alocasia macrorrhiza L. Schott - Zhi-Fang Lin; Nan Liu; Gui-Zhu Lin; Xiao-Ping Pan; Chang-Lian Peng (Journal of Fluorescence, 2007)

Cloning and functional characterization of PpDBF1 gene encoding a DRE-binding transcription factor from Physcomitrella patens - Ning Liu; Nai-Qin Zhong; Gui-Ling Wang; Li-Juan Li; Xiang-Lin Liu; Yi-Kun He; Gui-Xian Xia (Planta, 2007)

Mutation analysis of 218 Chinese patients with Wilson disease revealed no correlation between the canine copper toxicosis gene MURR1 and Wilson disease - Zhi-Ying Wu; Gui-Xian Zhao; Wan-Jin Chen; Ning Wang; Bo Wan; Min-Ting Lin; Shen-Xing Murong; Long Yu (Journal of Molecular Medicine, 2006)

Status of Biological Studies and Aquaculture Development of the Mud Crab, Scylla serrata, in China: An Experimental Ecological Studies - Wang Gui-zhong; Li Shao-jing; Zeng Chao-shu; Lin Shu-jun; Kong Xiang-hui; Ai Chun-xiang; Lin Qiong-wu (Aquaculture International, 2005)

Arbuscular mycorrhizal status of wild plants in saline-alkaline soils of the Yellow River Delta - Jian-Min Zhou; Xian-Gui Lin; Fa-Yuan Wang; Run-Jin Liu (Mycorrhiza, 2004)

Protective effects of daviditin A against endothelial damage induced by lysophosphatidylcholine - De-Jian Jiang; Jun-Lin Jiang; Gui-Shan Tan; Yan-Hua Du; Kang-Ping Xu; Yuan-Jian Li (Naunyn-Schmiedeberg's Archives of Pharmacology, 2003)

Chloroplast Transformation in Oilseed Rape - Bing-Kai Hou; Yi-Hua Zhou; Li-Hong Wan; Zhong-Lin Zhang; Gui-Fang Shen; Zheng-Hua Chen; Zan-Min Hu (Transgenic Research, 2003)

Daily changes in components of xanthophyll cycle and antioxidant systems in leaves of rice at different developing stage - Cheng-Wei Yang; Yi-Zhu Chen; Chang-Lian Peng; Duan Jun; Gui-Zhu Lin (Acta Physiologiae Plantarum, 2001)

Genetic Diversity among Different Clones of the Gynogenetic Silver Crucian Carp, Carassius auratus gibelio, Revealed by Transferrin and Isozyme Markers - Lin Yang; Shu-Ting Yang; Xue-Hong Wei; Jian-Fang Gui (Biochemical Genetics, 2001)

Conversion of trypsin into a selenium-containing enzyme by using chemical mutation - Jun-Qiu Liu; Ming-Shou Jiang; Gui-Min Luo; Gang-Lin Yan; Jia-Cong Shen (Biotechnology Letters, 1998)